Resin composition, cured product, method for producing same, and laminate
A resin composition with a silicone macromonomer and silane compound enhances curing, appearance, and durability, addressing issues of incompatibility and moisture resistance in automotive components, ensuring effective water runoff for sensors like millimeter wave radar and LIDAR.
Patent Information
- Application Number
- JP2022548357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-09-10
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2041-09-10
AI Technical Summary
Existing resin compositions for automotive components, such as car lamp lenses and emblem surfaces, face issues with high curing temperatures, incompatibility of components, reduced durability due to moisture resistance, and impaired appearance, especially when used in adverse weather conditions.
A resin composition comprising a silicone macromonomer with a polyalkoxane unit and a monomer having a specific functional group, along with a silane compound or its partial hydrolysis product, which is cured using photopolymerization, ensuring excellent adhesion and durability.
The composition provides a hardened layer with improved curing, appearance, weather resistance, and durability, allowing easy water runoff even under adverse conditions, suitable for automotive components like millimeter wave radar and LIDAR sensors.
Smart Images

Figure 0007626141000001 
Figure 0007626141000002 
Figure 0007626141000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a cured product, a method for producing the same, and a laminate. This application claims priority based on Japanese Patent Application No. 2020-153163, filed in Japan on September 11, 2020, and Japanese Patent Application No. 2020-198572, Japanese Patent Application No. 2020-199028, and Japanese Patent Application No. 2020-199037, filed in Japan on November 30, 2020, the contents of which are incorporated herein by reference. [Background technology]
[0002] Polymethyl methacrylate resin, polymethacrylimide resin, polycarbonate resin, polystyrene resin, acrylonitrile-styrene resin, etc. are used for components such as various lamp lenses, glazing, exteriors, and instrument covers for automobiles. Resin molded products made from these resins are lightweight, have excellent impact resistance, and have good transparency. Furthermore, in recent years, with the miniaturization of various components, transparent glass, which has excellent durability, has increasingly been used for cover members.
[0003] In recent years, vehicles such as automobiles are often equipped with advanced driver assistance systems (ADAS), including vehicle distance control systems, to ensure the safety of drivers, pedestrians, and oncoming vehicles. For example, examples of vehicle distance control systems include sensor devices (sometimes called millimeter wave radar) that use radio waves (millimeter waves) in the frequency band of about 30 to 300 GHz, and sensor devices (sometimes called LiDAR) that measure the characteristics and distance of objects using laser irradiation. The above-mentioned sensor device is often placed behind the emblem or front grille on the front of the vehicle in order to achieve both aesthetic appeal and aesthetic appeal. However, electromagnetic waves are easily attenuated and scattered by raindrops and snow, and if raindrops or snow adheres to the outermost surface of the emblem or front grille through which the electromagnetic waves pass, it can cause problems in measuring the distance to the target object. Therefore, the surface material of the emblem or front grille is required to have a water-repellent function that allows water droplets to slide off easily.
[0004] As a method for imparting water-sliding property to a substrate surface, a method of coating the substrate surface with a coating composition containing a resin having a polydimethylsiloxane structure is known.
[0005] Patent Document 1 proposes a coating composition that contains a silicone composition containing a tetrafunctional alkoxysilane and a trifunctional alkoxysilane or a partial hydrolysis condensate thereof, a reactive silicone having a specific structure including a polydimethylsiloxane structure, an acid or base catalyst, and water. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-132486 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, according to the study by the present inventors, the coating composition described in Patent Document 1 has a high curing temperature, so that this method is not suitable for, for example, a resin substrate. In addition, the compatibility between the component that contributes to water sliding property and other components is poor, so that the appearance of the formed coating layer is easily damaged. In addition, the durability of the coating layer is insufficient, and the appearance and water sliding property may be deteriorated by a moisture resistance test.
[0008] The present invention aims to provide a resin composition capable of forming a cured product excellent in appearance, water slippage and durability, a cured product excellent in appearance, water slippage, weather resistance and durability, a method for producing the same, and a laminate having a cured product layer excellent in appearance, water slippage, weather resistance and durability. [Means for solving the problem]
[0009] The present invention has the following aspects. [1] A copolymer (A) containing a structural unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a structural unit based on a monomer (Y) having a group represented by the following formula (1), and a component (B) consisting of a silane compound or a partial hydrolysis condensate thereof, a resin composition in which the sum of the proportion of structural units based on said silicone macromonomer (X) and the proportion of structural units based on said monomer (Y) is 55 mass% or more relative to the total mass of all structural units constituting said copolymer (A). -R 1 -M(R 2 ) r (OR 3 ) m-r (1) where M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta, and R 1 represents a hydrocarbon group having 1 to 5 carbon atoms, R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and if mr is 2 or more, (mr) ORs 3 may be different from each other. [2] The resin composition according to [1], wherein the component (B) comprises at least one silane compound represented by the following formula (b) or a partial hydrolysis condensate thereof: R 4 4-n Si(OR 5 ) n (b) However, R 4 represents a hydrogen atom, an alkyl group, an aryl group, or an aralkyl group; R 5 represents an alkyl group or a phenyl group, n represents an integer of 2 to 4, and n OR 5 may be different from each other, and when n is 2, (4-n) R 4 may be different from each other. [3] The resin composition according to [1] or [2], wherein the silicone macromonomer (X) has a weight average molecular weight of 500 to 40,000. [4] The resin composition according to any one of [1] to [3], wherein the proportion of the structural units based on the silicone macromonomer (X) is 15 to 60 mass % and the proportion of the structural units based on the monomer (Y) is 40 to 85 mass % relative to the total mass of all structural units constituting the copolymer (A). [5] The resin composition according to any one of [1] to [4], wherein the copolymer (A) has a weight average molecular weight of 3,000 to 400,000. [6] The resin composition according to any one of [1] to [5], wherein the weight average molecular weight of the component (B) is 500 or more. [7] The resin composition according to any one of [1] to [6], wherein the component (B) is a partial hydrolysis condensate of a tetraalkoxysilane. [8] The resin composition according to any one of [1] to [7], wherein the component (B) is a secondary reaction product obtained by subjecting a partial hydrolysis condensation product of at least one of the silane compounds having a weight-average molecular weight of 300 to 3,000 to a hydrolysis condensation reaction in the presence of a catalyst. [9] The resin composition according to any one of [1] to [8], further comprising an initiator (C).
[10] The resin composition according to [9], wherein the initiator (C) is a photopolymerization initiator.
[11] The resin composition according to [9] or
[10] , wherein the initiator (C) contains at least one selected from the group consisting of a photoacid generator and a photobase generator.
[12] The resin composition according to any one of [1] to
[11] , which is used for a sensing component.
[13] A cured product of the resin composition according to any one of [1] to
[12] .
[14] A copolymer (A) containing a structural unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a structural unit based on a monomer (Y) having a group represented by the following formula (1), and a component (B) consisting of a silane compound or a partial hydrolysis condensate thereof, After a 96-hour durability test under conditions of a tank temperature of 50°C and a tank humidity of 99% RH or higher, the cured product has a surface where the sliding angle of 20 μL of distilled water at 23°C is 60° or less, as measured by tilting the substrate with an intermittent tilt angle that is changed intermittently by 1°. -R 1 -M(R 2 ) r (OR 3 ) m-r (1) where M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta, and R 1 represents a hydrocarbon group having 1 to 5 carbon atoms, R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and if mr is 2 or more, (mr) ORs 3 may be different from each other.
[15] A laminate comprising a substrate and a layer made of the cured product according to
[14] .
[16] A laminate comprising a primer layer provided on a substrate, and a layer of the cured product according to
[14] provided on the primer layer.
[17] A resin composition comprising: a copolymer (A) containing a constituent unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a constituent unit based on a monomer (Y) having a group represented by the following formula (1); a component (B) consisting of a silane compound or a partial hydrolysis condensate thereof; and a photopolymerization initiator: -R 1 -M(R 2 ) r (OR 3 ) m-r (1) where M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta, and R 1 represents a hydrocarbon group having 1 to 5 carbon atoms, R 2represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and if mr is 2 or more, (mr) ORs 3 may be different from each other.
[18] A cured product comprising: a copolymer (A) containing a constituent unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a constituent unit based on a monomer (Y) having a group represented by the following formula (1); a component (B) consisting of a silane compound or a partial hydrolysis condensate thereof; and a photopolymerization initiator. -R 1 -M(R 2 ) r (OR 3 ) m-r (1) where M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta, and R 1 represents a hydrocarbon group having 1 to 5 carbon atoms, R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and if mr is 2 or more, (mr) ORs 3 may be different from each other.
[19] A method for producing a cured product, comprising curing a resin composition comprising: a copolymer (A) containing a constituent unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a constituent unit based on a monomer (Y) having a group represented by the following formula (1); and a component (B) containing a silane compound or a partial hydrolysis condensate thereof, by a heat treatment or exposure to active energy rays: -R 1 -M(R 2 )r (OR 3 ) m-r (1) where M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta, and R 1 represents a hydrocarbon group having 1 to 5 carbon atoms, R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and if mr is 2 or more, (mr) ORs 3 may be different from each other. Effect of the Invention
[0010] Effects of the Invention According to the present invention, it is possible to provide a resin composition that has excellent curing properties and can form a cured product that is excellent in appearance, water slippage, weather resistance and durability, a cured product that is excellent in appearance, water slippage, weather resistance and durability, a method for producing the same, and a laminate having a cured product layer that is excellent in appearance, water slippage, weather resistance and durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The following describes in detail an embodiment of the present invention. However, the following description is an example of an embodiment of the present invention, and the present invention is not limited to the contents of the following description as long as it does not go beyond the gist of the present invention. In this specification, when the expression "~" is used, it is used as an expression including the numerical value or physical property value before and after it. Furthermore, in the present invention, when the expression "(meth)acrylic" is used, it means one or both of "acrylic" and "methacrylic". The same applies to "(meth)acrylate", "(meth)acryloyl", etc.
[0012] [Resin composition] A resin composition according to one embodiment of the present invention (hereinafter also referred to as "the resin composition") contains a copolymer (A) containing a polydimethylsiloxane unit, and a component (B) consisting of at least one specific silane compound or a partial hydrolysis condensate thereof. The present resin composition may further contain an initiator (C) and a diluent, if necessary. The present resin composition may further contain other components in addition to those described above, as necessary.
[0013] <Copolymer (A)> The copolymer (A) contains a polyalkylsiloxane unit. By including the copolymer (A) containing a polyalkylsiloxane unit, the cured product of the present resin composition exhibits water-sliding properties. The polyalkylsiloxane unit contains two or more alkylsiloxane units. The polyalkylsiloxane unit may be, for example, a linear type, a branched type, or a dendrimer type. Among these, -(Si(R 18 )2O) n It is preferable that the polyalkylsiloxane unit contains a linear polyalkylsiloxane unit represented by the formula R 18 represents a hydrocarbon group having 1 to 10 carbon atoms, preferably a hydrocarbon group having 1 to 5 carbon atoms, and more preferably a methyl group. n represents the average degree of polymerization of the polyalkylsiloxane unit. The average degree of polymerization of the polyalkylsiloxane units is preferably 5 to 1000, more preferably 10 to 500, further preferably 30 to 300, and particularly preferably 50 to 200. When the average degree of polymerization is equal to or more than the above lower limit, the cured product of the resin composition has better water slidability, and when it is equal to or less than the above upper limit, the monomer having the polyalkylsiloxane units (the silicone macromonomer (X) described below) tends to be more compatible with other monomers, making it easier to produce the copolymer (A).
[0014] The copolymer (A) may contain a polyalkylsiloxane unit in the main chain, in the side chain, or in both the main chain and the side chain. In terms of water-repellent properties and ease of production of the copolymer (A), it is preferable that the copolymer (A) contains a polydimethylsiloxane unit at least in the side chain.
[0015] As the copolymer (A) containing a polyalkylsiloxane unit at least in a side chain, in consideration of the ease of introducing the polyalkylsiloxane unit and the ease of controlling performance such as slipperiness, a copolymer containing a structural unit (hereinafter also referred to as "structural unit (X)") based on a silicone macromonomer (X) (hereinafter also referred to as "macromonomer (X)") containing a polyalkylsiloxane unit is preferred. From the viewpoint of improving performance such as water slipping property, it is preferable that the copolymer (A) further contains a structural unit based on a monomer (Y) having a group represented by a specific formula (1) (hereinafter also referred to as "structural unit (Y)"). The copolymer (A) may further contain, as necessary, a structural unit based on a monomer (Z) other than the macromonomer (X) and the monomer (Y) (hereinafter, also referred to as "structural unit (Z)"), provided that the performance is not impaired.
[0016] (Silicone macromonomer (X)) The silicone macromonomer (X) may be a compound containing a polyalkylsiloxane unit and a polymerizable functional group. The polymerizable functional group may be any group containing a polymerizable unsaturated bond such as a polymerizable carbon-carbon double bond, and examples thereof include a (meth)acryloyl group, a vinyl group, a (meth)acrylamide group, etc. Among these, a (meth)acryloyl group is preferred from the viewpoint of ease of copolymerization with other monomers. The polyalkylsiloxane unit and the polymerizable functional group may be bonded via a linking group, for example, a hydrocarbon group such as an alkylene group having 1 to 6 carbon atoms.
[0017] An example of the silicone macromonomer (X) having a (meth)acryloyl group is a compound represented by the following formula (2). CH2=CR 19 -CO-OR 20 -(Si(R 18 )2O) n -R 21 (2) However, R 18 represents a hydrocarbon group having 1 to 10 carbon atoms, n represents the average degree of polymerization, and R 19 represents a hydrogen atom or a methyl group, R 20 represents a hydrocarbon group having 1 to 10 carbon atoms, R 21 represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, or an aryl group. The preferred range of n is the same as the preferred range of the average degree of polymerization of the polyalkylsiloxane units described above. Among these, R 18 represents a hydrocarbon group having 1 to 10 carbon atoms, preferably a hydrocarbon group having 1 to 5 carbon atoms, more preferably a methyl group; R 19 is preferably a methyl group, R 20 is preferably a hydrocarbon group having 1 to 6 carbon atoms, more preferably a hydrocarbon group having 2 to 4 carbon atoms; R 21 is preferably a hydrocarbon group having 1 to 6 carbon atoms, and more preferably a hydrocarbon group having 1 to 4 carbon atoms.
[0018] The weight average molecular weight (hereinafter also referred to as "Mw") of the silicone macromonomer (X) is preferably 500 to 40,000, more preferably 700 to 30,000, even more preferably 800 to 20,000, particularly preferably 1,000 to 18,000, and most preferably 2,000 to 15,000. When the Mw of the silicone macromonomer (X) is at least the above lower limit, the cured product of the resin composition has better water slidability, whereas when it is at most the above upper limit, the silicone macromonomer (X) is more compatible with the monomer (Y) and the monomer (Z), tending to facilitate the production of the copolymer (A). The Mw of the silicone macromonomer (X) is a value calculated in terms of standard polystyrene as measured by gel permeation chromatography (GPC).
[0019] As the silicone macromonomer (X), commercially available products can be used. As commercially available products of the linear silicone macromonomer (X), for example, Silaplane (registered trademark) FM-0711 (number average molecular weight listed in the catalog: 1000), Silaplane FM-0721 (number average molecular weight listed in the catalog: 5000), Silaplane FM-0725 (number average molecular weight listed in the catalog: 10000) manufactured by JNC; X-22-174ASX (number average molecular weight listed in the catalog: 900), X-22-174BX (number average molecular weight listed in the catalog: 2300), KF-2012 (number average molecular weight listed in the catalog: 4600), X-22-2426 (number average molecular weight listed in the catalog: 12000) manufactured by Shin-Etsu Chemical Co., Ltd., and the like can be mentioned. As the dendrimer type silicone macromonomer (X), for example, HGO-3002 manufactured by Silicon Material Development Co., Ltd. can be mentioned. The silicone macromonomer (X) may be used alone or in combination of two or more kinds.
[0020] (Monomer (Y)) Monomer (Y) has a group represented by the following formula (1) (hereinafter also referred to as "group (1)"). When group (1) is introduced into copolymer (A) by monomer (Y), group (1) in copolymer (A) reacts with component (B), which makes it possible to suppress bleeding out of polydimethylsiloxane units onto the surface of the cured product of the present resin composition, thereby improving durability. -R 1 -M(R 2 ) r (OR 3 ) m-r (1) where M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta, and R 1 represents a hydrocarbon group having 1 to 5 carbon atoms, R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2may be different from each other, and when mr is 2 or more, (mr) R 3 may be different from each other.
[0021] In formula (1), M may be any one of Al (aluminum), Fe (iron), In (indium), Ge (germanium), Hf (hafnium), Si (silicon), Ti (titanium), Sn (tin), Zr (zirconium), and Ta (tantalum). From the viewpoints of reactivity and availability, Al, Si, Ti, or Zr is preferred, and Si is particularly preferred because it is inexpensive and easy to use.
[0022] R 2 and R 3 Examples of the aryl group include a phenyl group, a toluyl group, and a naphthyl group. R 2 and R 3 The alkyl group, alkenyl group and aryl group may each have a substituent, for example, a halogen atom such as a chlorine atom, and an alkoxy group such as a methoxy group or an ethoxy group. R 3 Examples of the acyl group include a (meth)acryl group, an acetyl group, an acetimidoyl group, an aldehyde group, a thioacetyl group, a propionyl group, a benzenesulfonyl group, and a benzoyl group.
[0023] OR 3 can be subdivided into alkoxy groups, alkenyloxy groups, aryloxy groups, acyloxy groups, ketoximate groups, and hydroxy groups. Among these, alkoxy groups, alkenyloxy groups, acyloxy groups, and hydroxy groups are preferred because of their high reactivity, and alkoxy groups such as methoxy groups and ethoxy groups, and hydroxy groups are particularly preferred because of their easy control of hydrolysis and ease of handling.
[0024] Examples of the group (1) (also referred to as a hydrolyzable silyl group) when M in formula (1) is Si include a trimethoxysilyl group, a triethoxysilyl group, a triisopropoxysilyl group, a dimethoxymethylsilyl group, a diethoxymethylsilyl group, a diisopropoxymethylsilyl group, a tris(2-propenyloxy)silyl group, a (chloromethyl)dimethoxysilyl group, a (methoxymethyl)dimethoxysilyl group, a (methoxymethyl)diethoxysilyl group, and an (ethoxymethyl)dimethoxysilyl group. Among the above, trimethoxysilyl, triethoxysilyl, and dimethoxymethylsilyl groups are preferred from the viewpoint of general-purpose, high activity, and good curability, and dimethoxymethylsilyl groups are more preferred. From the viewpoint of storage stability, dimethoxymethylsilyl and triethoxysilyl groups are preferred. From the viewpoint of particularly high curability, (chloromethyl)dimethoxysilyl and (methoxymethyl)dimethoxysilyl groups are preferred. From the viewpoint of a tendency for the restoration of the cured product to be high, trifunctional silyl groups such as trimethoxysilyl and triethoxysilyl groups are preferred.
[0025] Examples of the monomer (Y) include a compound having the above-mentioned group (1) and a polymerizable functional group or a reactive group capable of being added to a polymer (polymer reaction). Examples of the polymerizable functional group include the same as those described above, and preferred embodiments are also the same. Examples of the reactive group include a vinyl group, a (meth)acryloyl group, a (meth)acrylamide group, an epoxy group, a cyclic epoxy group, a mercapto group, an amino group, a diamino group, an acid anhydride group, and an isocyanate group. The group (1) and the polymerizable functional group or reactive group may be bonded via a linking group, for example, a hydrocarbon group such as an alkylene group having 1 to 6 carbon atoms.
[0026] Examples of the monomer (Y) include vinyl-based silane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, (3-trimethoxysilyl)propyl (meth)acrylate, (3-dimethoxymethylsilyl)propyl (meth)acrylate, (2-trimethoxysilyl)ethyl (meth)acrylate, (2-dimethoxymethylsilyl)ethyl (meth)acrylate, trimethoxysilylmethyl (meth)acrylate, and (dimethoxymethylsilyl)methyl (meth)acrylate; γ-aminopropyltrimethoxysilane, N-β-(aminoethyl) ... Examples of silane coupling agents include amino-based silane compounds such as aminopropyltrimethoxysilane, N-β-(aminoethyl)γ-aminopropylmethyldimethoxysilane, and γ-ureidopropyltriethoxysilane, epoxy-based silane compounds such as γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and γ-glycidoxypropylmethyldiethoxysilane, mercapto-based silane compounds such as γ-mercaptopropyltrimethoxysilane, and phenylamino-based silane compounds such as N-phenyl-γ-aminopropyltrimethoxysilane. These silane coupling agents are commercially available and are preferred from the viewpoints of price and ease of handling. However, the monomer (Y) is not limited to these. For example, a titanate-, aluminate- or zirconate-based coupling agent having a polymerizable functional group capable of copolymerizing with other monomers or a reactive group other than the group (1) capable of being added to a polymer may be used. The monomer (Y) may be used alone or in combination of two or more kinds.
[0027] When the silicone macromonomer (X) and the monomer (Y) are copolymerized, the better the copolymerizability between the silicone macromonomer (X) and the monomer (Y), the more the amount of unreacted monomer can be reduced, and the durability of the cured product of the resin composition tends to improve. From this viewpoint, when the polymerizable functional group of the silicone macromonomer (X) is a (meth)acryloyl group, the monomer (Y) is particularly preferably a vinyl-based silane compound having a (meth)acryloyl group.
[0028] (Monomer (Z)) The monomer (Z) may be any monomer that is copolymerizable with the silicone macromonomer (X), and examples thereof include the above-mentioned compounds having a polymerizable functional group (excluding the silicone macromonomer (X) and the monomer (Y)).
[0029] Specific examples of the monomer (Z) include the following. Methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, toluyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, (Meth)acrylic acid monomers such as stearyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, ethylene oxide adducts of (meth)acrylic acid, trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, perfluoroethyl (meth)acrylate, trifluoromethyl (meth)acrylate, bis(trifluoromethyl)methyl (meth)acrylate, 2-trifluoromethyl-2-perfluoroethylethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, and 2-perfluorohexadecylethyl (meth)acrylate. (Meth)acrylamide-based monomers such as (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, Nn-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-dimethylaminoethyl(meth)acrylamide, N-dimethylaminopropyl(meth)acrylamide, diacetone(meth)acrylamide, N-(meth)acryloylpiperidine, and (meth)acroylmorpholine.
[0030] Styrenic monomers such as styrene, vinyltoluene, α-methylstyrene, chlorostyrene, styrenesulfonic acid and its salts. Maleic anhydride, maleic acid, the mono- and dialkyl esters of maleic acid; fumaric acid, the mono- and dialkyl esters of fumaric acid. Maleimide monomers such as maleimide, methylmaleimide, ethylmaleimide, propylmaleimide, butylmaleimide, hexylmaleimide, octylmaleimide, dodecylmaleimide, stearylmaleimide, phenylmaleimide, and cyclohexylmaleimide. Nitrile group-containing vinyl monomers such as acrylonitrile and methacrylonitrile. Amide group-containing vinyl monomers such as acrylamide and methacrylamide. Vinyl esters such as vinyl acetate, vinyl propionate, vinyl pivalate, vinyl benzoate, and vinyl cinnamate. Alkenes such as ethylene and propylene. Conjugated dienes such as butadiene and isoprene. Vinyl chloride, vinylidene chloride, allyl chloride, allyl alcohol, etc. The monomer (Z) may be used alone or in combination of two or more kinds.
[0031] When the silicone macromonomer (X) and the monomer (Z) are copolymerized, the better the copolymerizability between the silicone macromonomer (X) and the monomer (Z), the more the amount of unreacted monomer can be reduced, and the durability of the cured product of the resin composition tends to improve. From this viewpoint, when the polymerizable functional group of the silicone macromonomer (X) is a (meth)acryloyl group, the monomer (Z) is preferably at least one selected from a styrene-based monomer and a (meth)acrylic acid-based monomer, and a (meth)acrylic acid-based monomer is particularly preferred.
[0032] (Proportion of each structural unit in copolymer (A)) The proportion of the structural unit (X) relative to the total mass of all structural units constituting the copolymer (A) is preferably 15 to 60 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 50 mass%. When the proportion of the structural unit (X) is at least the lower limit above, the water slippage of the cured product becomes better, and when it is at or below the upper limit above, the amount of unpolymerized silicone macromonomer (X) can be reduced, so the transparency of the cured product tends to be good.
[0033] The proportion of the structural unit (Y) relative to the total mass of all structural units constituting the copolymer (A) is preferably 40 to 85 mass%, more preferably 40 to 80 mass%, and even more preferably 40 to 75 mass%. If the proportion of the structural unit (Y) is equal to or greater than the lower limit, the durability of the cured product will be better, and if it is equal to or less than the upper limit, the proportion of the structural unit (X) can be made sufficiently high, so that the water sliding properties of the cured product tend to be good.
[0034] The total of the proportion of the silicone macromonomer (X)-based structural units and the proportion of the monomer (Y)-based structural units relative to the total mass of all structural units constituting the copolymer (A) is preferably 55% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 100% by mass. If the total proportion of the structural units (X) and (Y) is equal to or more than the lower limit, the durability and water slippage of the cured product tend to be improved.
[0035] The ratio of the structural unit (Z) to the total mass of all structural units constituting the copolymer (A) is preferably 0 to 45% by mass, more preferably 0 to 40% by mass, even more preferably 0 to 30% by mass, particularly preferably 0 to 20% by mass, and most preferably 0 to 10% by mass. The lower the ratio of the structural unit (Z), the better the water slipping property of the cured product tends to be. On the other hand, the higher the ratio of the structural unit (Z), the better the copolymerization property when producing the copolymer (A). The proportion of each structural unit can be determined by an analytical method such as a nuclear magnetic resonance method or an infrared spectroscopic analysis using a total reflection method.
[0036] (Mw of copolymer (A)) The Mw of the copolymer (A) is preferably 3000 to 400000, more preferably 5000 to 100000, and particularly preferably 7000 to 80000. Further, it is more preferably 8000 to 40000. When the Mw of the copolymer (A) is equal to or greater than the lower limit, the copolymer (A) is firmly fixed in the cured product, so that the water slipping property and durability tend to be improved, and when it is equal to or less than the upper limit, the compatibility with other components in the resin composition is improved, so that the appearance of the cured product tends to be improved. The Mw of the copolymer (A) is a value calculated in terms of standard polystyrene as measured by gel permeation chromatography (GPC).
[0037] (Method for producing copolymer (A)) The method for producing the copolymer (A) is not particularly limited, and any known method can be appropriately adopted. For example, a copolymer having the structural unit (X) and the structural unit (Y) can be produced by the following method (i) or (ii). (i) A method of polymerizing a monomer mixture containing a silicone macromonomer (X), a monomer (Y) containing a polymerizable functional group, and, as necessary, a monomer (Z). (ii) A method of polymerizing a monomer mixture containing a silicone macromonomer (X) and, if necessary, a monomer (Z), and reacting the resulting polymer with a monomer (Y) containing a reactive group capable of being added to the polymer.
[0038] In methods (i) and (ii), the proportion of the silicone macromonomer (X) relative to the total mass of the silicone macromonomer (X), the monomer (Y) and the monomer (Z) is preferably 15 to 60 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 50 mass%. If the proportion of the silicone macromonomer (X) is equal to or greater than the lower limit, the cured product will have better water slippage, and if it is equal to or less than the upper limit, the amount of unpolymerized silicone macromonomer (X) can be reduced, so that the transparency of the cured product tends to be good.
[0039] The proportion of monomer (Y) relative to the total mass of silicone macromonomer (X), monomer (Y) and monomer (Z) is preferably 40 to 85 mass%, more preferably 40 to 80 mass%, and even more preferably 40 to 75 mass%. When the proportion of monomer (Y) is equal to or greater than the lower limit, the durability of the cured product is improved, whereas when the proportion of monomer (Y) is equal to or less than the upper limit, the proportion of silicone macromonomer (X) can be made sufficiently high, and the cured product tends to have good water slippage.
[0040] The proportion of monomer (Z) relative to the total mass of silicone macromonomer (X), monomer (Y) and monomer (Z) is preferably 0 to 45% by mass, more preferably 0 to 40% by mass, even more preferably 0 to 30% by mass, particularly preferably 0 to 20% by mass, and most preferably 0 to 10% by mass. The lower the proportion of monomer (Z), the better the water slipping property of the cured product tends to be. On the other hand, the higher the proportion of monomer (Z), the better the copolymerizability of the monomer mixture tends to be. In particular, in applications where water sliding property is important, it is preferable to increase the content of the silicon atom-containing compound as much as possible, and therefore it is preferable that the structural unit (Z) is not contained.
[0041] In the methods (i) and (ii), the method for polymerizing the monomer mixture is not particularly limited, and any known polymerization method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization can be used. The polymerization conditions are not particularly limited, but may be, for example, at 30 to 180° C. for 0.5 to 24 hours.
[0042] The monomer mixture is preferably polymerized in the presence of a polymerization initiator. As the polymerization initiator, various known polymerization initiators can be used. For example, azonitrile compounds such as 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V-70, Fujifilm Wako Pure Chemical Industries, Ltd.), 2,2'-azobis(2,4-dimethylvaleronitrile) (V-65, Fujifilm Wako Pure Chemical Industries, Ltd.), 2,2'-azobisisobutyronitrile (V-60, Fujifilm Wako Pure Chemical Industries, Ltd.), and 2,2'-azobis(2-methylbutyronitrile) (V-59, Fujifilm Wako Pure Chemical Industries, Ltd.); octanoyl peroxide (Perloyl (registered trademark) O, NOF Corp.), lauroyl peroxide, diacyl peroxides such as peroxide (Perloil L, manufactured by NOF Corp.), stearoyl peroxide (Perloil S, manufactured by NOF Corp.), succinic acid peroxide (Perloil SA, manufactured by NOF Corp.), benzoyl peroxide (Niper (registered trademark) BW, manufactured by NOF Corp.), isobutyryl peroxide (Perloil IB, manufactured by NOF Corp.), 2,4-dichlorobenzoyl peroxide (Niper CS, manufactured by NOF Corp.), and 3,5,5-trimethylhexanoyl peroxide (Perloil 355, manufactured by NOF Corp.); di-n-propyl peroxydicarbonate (Per Peroxydicarbonate (Peroyl NPP-50M, NOF Corp.), diisopropyl peroxydicarbonate (Peroyl IPP-50, NOF Corp.), bis(4-t-butylcyclohexyl) peroxydicarbonate (Peroyl TCP, NOF Corp.), di-2-ethoxyethyl peroxydicarbonate (Peroyl EEP, NOF Corp.), di-2-ethoxyhexyl peroxydicarbonate (Peroyl OPP, NOF Corp.), di-2-methoxybutyl peroxydicarbonate (Peroyl MBP, NOF Corp.), di(3-methyl-3-methoxybutyl ) peroxydicarbonates such as peroxydicarbonate (Peroyl SOP, manufactured by NOF Corp.); hydroperoxides such as t-butyl hydroperoxide (Perbutyl (registered trademark) H-69, manufactured by NOF Corp.), 1,1,3,3-tetramethylbutyl hydroperoxide (Perocta (registered trademark) H, manufactured by NOF Corp.); dialkyl peroxides such as di-t-butyl peroxide (Perbutyl D, manufactured by NOF Corp.), 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane (Perhexa (registered trademark) 25B, manufactured by NOF Corp.);α,α'-Bis(neodecanoylperoxy)diisopropylbenzene (Diper(R) ND, manufactured by NOF Corp.), cumyl peroxy neodecanoate (Percumyl(R) ND, manufactured by NOF Corp.), 1,1,3,3-tetramethylbutyl peroxy neodecanoate (Perocta ND, manufactured by NOF Corp.), 1-cyclohexyl-1-methylethyl peroxy neodecanoate (Percyclo(R) ND, manufactured by NOF Corp.), t-hexyl peroxy neodecanoate (Perhexyl(R) ND, manufactured by NOF Corp.), t-butyl peroxy neodecanoate (Perbutyl ND, manufactured by NOF Corp.), t-hexyl peroxy pivalate (Perhexyl PV, manufactured by NOF Corp.), t-butyl peroxy pivalate (Perbutyl PV, manufactured by NOF Corp.), 1,1,3,3-tetramethylbutyl Examples of the peroxyester include organic peroxides such as peroxy-2-ethylhexanoate (Perocta O, manufactured by NOF Corp.), 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane (Perhexa 250, manufactured by NOF Corp.), 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate (Percyclo O, manufactured by NOF Corp.), t-hexylperoxy 2-ethylhexanoate (Perhexyl O, manufactured by NOF Corp.), t-butylperoxy 2-ethylhexanoate (Perbutyl O, manufactured by NOF Corp.), t-butylperoxyisobutyrate (Perbutyl IB, manufactured by NOF Corp.), t-hexylperoxyisopropyl monocarbonate (Perhexyl I, manufactured by NOF Corp.), and t-butylperoxymaleic acid (Perbutyl MA, manufactured by NOF Corp.). However, the polymerization initiator is not particularly limited to these.; The polymerization initiator may be used alone or in combination of two or more kinds. The amount of the polymerization initiator used is, for example, 0.01 to 10 parts by mass with respect to 100 parts by mass of the monomer mixture.
[0043] In the method (ii), examples of the method for reacting the polymer with the monomer (Y) include, but are not limited to, a method in which a silicone macromonomer (X) is copolymerized with a monomer (Z) containing a hydroxyl group, and then an addition reaction is carried out with an isocyanate group and a compound containing a group (1).
[0044] <Ingredient (B)> Component (B) comprises at least one silane compound represented by the following formula (b) (hereinafter also referred to as "silane compound (b)") or a partial hydrolysis condensate thereof. R 4 4-n Si(OR 5 ) n (b) However, R 4 represents a hydrogen atom, an alkyl group, an aryl group, or an aralkyl group; R 5 represents an alkyl group or a phenyl group, n represents an integer of 2 to 4, and n OR 5 may be different from each other, and when n is 2, (4-n) R 4 may be different from each other.
[0045] In formula (b), R 4 The alkyl group may be linear or branched. The alkyl group preferably has 1 to 20 carbon atoms, and more preferably has 1 to 4 carbon atoms. Examples of the aryl group include a phenyl group, a toluyl group, and a naphthyl group. Examples of the aralkyl group include a benzyl group and a phenethyl group.
[0046] R 5 The alkyl group may be linear or branched, and is preferably linear from the viewpoint of hydrolysis rate. The number of carbon atoms in the alkyl group is preferably 1 to 5, more preferably 1 or 2, and even more preferably 1, from the viewpoint of hydrolysis rate.
[0047] The silane compound in which n in formula (b) is 4 (hereinafter also referred to as "silane compound (b1)") is represented by the following formula (b1). Si(OR 6 ) a (OR 7 ) b (OR 8 ) c (OR 9 ) d (b1) However, R 6 , R 7 , R 8and R 9 each independently represents an alkyl group or a phenyl group, and a, b, c, and d are integers satisfying the condition 0≦a≦4, 0≦b≦4, 0≦c≦4, and 0≦d≦4, and a+b+c+d=4. R 6 , R 7 , R 8 and R 9 is the above R 5 is the same as:
[0048] The silane compound in which n in formula (b) is 3 (hereinafter also referred to as "silane compound (b2)") is represented by the following formula (b2). R 10 Si(OR 11 ) e (OR 12 ) f (OR 13 ) g (b2) However, R 10 R represents a hydrogen atom, an alkyl group, an aryl group, or an aralkyl group. 11 , R 12 and R 13 each independently represents an alkyl group or a phenyl group, and e, f, and g are integers satisfying the condition 0≦e≦3, 0≦f≦3, and 0≦g≦3 and e+f+g=3. R 10 is the above R 4 Same as R 11 , R 12 and R 13 is the above R 5 is the same as:
[0049] The silane compound in which n in formula (b) is 2 (hereinafter also referred to as "silane compound (b3)") is represented by the following formula (b3). R 14 R 15 Si(OR 16 ) h (OR 17 ) i (b3) However, R 14 and R 15R each independently represents a hydrogen atom, an alkyl group, an aryl group, or an aralkyl group. 16 and R 17 each independently represents an alkyl group or a phenyl group, and h and i are integers satisfying the conditions 0≦h≦2 and 0≦i≦2 and h+i=2. R 14 and R 15 is the above R 4 Same as R 16 and R 17 is the above R 5 is the same as:
[0050] Specific examples of the silane compound (b1) include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, tetrapentyloxysilane, tetraphenyloxysilane, trimethoxymonoethoxysilane, dimethoxydiethoxysilane, triethoxymonomethoxysilane, trimethoxymonopropoxysilane, monomethoxytributoxysilane, monomethoxytripentyloxysilane, monomethoxytriphenyloxysilane, dimethoxydipropoxysilane, tripropoxymonomethoxysilane, trimethoxymonobutoxysilane, dimethoxydibutoxysilane, and triethoxymonopropoxysilane. Examples of tetraalkoxysilanes include tetraalkoxysilanes such as silane, diethoxydipropoxysilane, tributoxymonopropoxysilane, dimethoxymonoethoxymonobutoxysilane, diethoxymonomethoxymonobutoxysilane, diethoxymonopropoxymonobutoxysilane, dipropoxymonomethoxymonoethoxysilane, dipropoxymonomethoxymonobutoxysilane, dipropoxymonoethoxymonobutoxysilane, dibutoxymonomethoxymonoethoxysilane, dibutoxymonoethoxymonopropoxysilane, and monomethoxymonoethoxymonopropoxymonobutoxysilane, and among these, tetramethoxysilane and tetraethoxysilane are preferred.
[0051] Specific examples of the silane compound (b2) include hydrosilane compounds such as trimethoxysilane, triethoxysilane, tripropoxysilane, tripentyloxysilane, triphenyloxysilane, dimethoxymonoethoxysilane, diethoxymonomethoxysilane, dipropoxymonomethoxysilane, dipropoxymonoethoxysilane, dipentyloxylmonomethoxysilane, dipentyloxymonoethoxysilane, dipentyloxymonopropoxysilane, diphenyloxylmonomethoxysilane, diphenyloxymonoethoxysilane, diphenyloxymonopropoxysilane, methoxyethoxypropoxysilane, monopropoxydimethoxysilane, monopropoxydiethoxysilane, monobutoxydimethoxysilane, monopentyloxydiethoxysilane, and monophenyloxydiethoxysilane;
[0052] Methylsilane compounds such as methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, methyltripentyloxysilane, methyltriphenyloxysilane, methylmonomethoxydiethoxysilane, methylmonomethoxydipropoxysilane, methylmonomethoxydipentyloxysilane, methylmonomethoxydiphenyloxysilane, methylmethoxyethoxypropoxysilane, and methylmonomethoxymonoethoxymonobutoxysilane; ethylsilane compounds such as ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane, ethyltripentyloxysilane, ethyltriphenyloxysilane, ethylmonomethoxydiethoxysilane, ethylmonomethoxydipropoxysilane, ethylmonomethoxydipentyloxysilane, ethylmonomethoxydiphenyloxysilane, ethylmethoxyethoxypropoxysilane, and ethylmonomethoxymonoethoxymonobutoxysilane;
[0053] Propyl silane compounds such as propyl trimethoxy silane, propyl triethoxy silane, propyl tripropoxy silane, propyl tripentyloxy silane, and propyl triphenyloxy silane, propyl monomethoxy diethoxy silane, propyl monomethoxy dipropoxy silane, propyl monomethoxy dipentyloxy silane, propyl monomethoxy diphenyloxy silane, propyl methoxy ethoxy propoxy silane, and propyl monomethoxy monoethoxy monobutoxy silane;
[0054] butyl silane compounds such as butyl trimethoxy silane, butyl triethoxy silane, butyl tripropoxy silane, butyl tripentyloxy silane, butyl triphenyloxy silane, butyl monomethoxy diethoxy silane, butyl monomethoxy dipropoxy silane, butyl monomethoxy dipentyloxy silane, butyl monomethoxy diphenyloxy silane, butyl methoxy ethoxy propoxy silane, and butyl monomethoxy monoethoxy monobutoxy silane;
[0055] Phenylsilane compounds such as phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrippropoxysilane, phenyltripentyloxysilane, phenyltriphenyloxysilane, phenylmonomethoxydiethoxysilane, phenylmonomethoxydipropoxysilane, phenylmonomethoxydipentyloxysilane, phenylmonomethoxydiphenyloxysilane, phenylmethoxyethoxypropoxysilane, and phenylmonomethoxymonoethoxymonobutoxysilane;
[0056] hydroxyphenylsilane compounds such as hydroxyphenyltrimethoxysilane, hydroxyphenyltriethoxysilane, hydroxyphenyltripropoxysilane, hydroxyphenyltripentyloxysilane, hydroxyphenyltriphenyloxysilane, hydroxyphenylmonomethoxydiethoxysilane, hydroxyphenylmonomethoxydipropoxysilane, hydroxyphenylmonomethoxydipentyloxysilane, hydroxyphenylmonomethoxydiphenyloxysilane, hydroxyphenylmethoxyethoxypropoxysilane, and hydroxyphenylmonomethoxymonoethoxymonobutoxysilane;
[0057] naphthylsilane compounds such as naphthyltrimethoxysilane, naphthyltriethoxysilane, naphthyltripropoxysilane, naphthyltripentyloxysilane, naphthyltriphenyloxysilane, naphthylmonomethoxydiethoxysilane, naphthylmonomethoxydipropoxysilane, naphthylmonomethoxydipentyloxysilane, naphthylmonomethoxydiphenyloxysilane, naphthylmethoxyethoxypropoxysilane, and naphthylmonomethoxymonoethoxymonobutoxysilane;
[0058] benzyl silane compounds such as benzyl trimethoxysilane, benzyl triethoxysilane, benzyl tripropoxysilane, benzyl tripentyloxysilane, benzyl triphenyloxysilane, benzyl monomethoxy diethoxysilane, benzyl monomethoxy dipropoxysilane, benzyl monomethoxy dipentyloxysilane, benzyl monomethoxy diphenyloxysilane, benzyl methoxyethoxypropoxysilane, and benzyl monomethoxy monoethoxy monobutoxysilane;
[0059] Examples of hydroxybenzyl silane compounds include hydroxybenzyl trimethoxysilane, hydroxybenzyl triethoxysilane, hydroxybenzyl tripropoxysilane, hydroxybenzyl tripentyloxysilane, hydroxybenzyl triphenyloxysilane, hydroxybenzyl monomethoxy diethoxysilane, hydroxybenzyl monomethoxy dipropoxysilane, hydroxybenzyl monomethoxy dipentyloxysilane, hydroxybenzyl monomethoxy diphenyloxysilane, hydroxybenzyl methoxyethoxypropoxysilane, and hydroxybenzyl monomethoxy monoethoxy monobutoxysilane.
[0060] Specific examples of the silane compound (b3) include hydrosilane compounds such as dimethoxysilane, diethoxysilane, dipropoxysilane, dipentyloxysilane, diphenyloxysilane, methoxyethoxysilane, methoxypropoxysilane, methoxypentyloxysilane, methoxyphenyloxysilane, ethoxypropoxysilane, ethoxypentyloxysilane, and ethoxyphenyloxysilane;
[0061] Methylhydrosilane compounds such as methyldimethoxysilane, methylmethoxyethoxysilane, methyldiethoxysilane, methylmethoxypropoxysilane, methylmethoxypentyloxysilane, methylethoxypropoxysilane, methyldipropoxysilane, methyldipentyloxysilane, methyldiphenyloxysilane, and methylmethoxyphenyloxysilane;
[0062] Ethylhydrosilane compounds such as ethyldimethoxysilane, ethylmethoxyethoxysilane, ethyldiethoxysilane, ethylmethoxypropoxysilane, ethylmethoxypentyloxysilane, ethylethoxypropoxysilane, ethyldipropoxysilane, ethyldipentyloxysilane, ethyldiphenyloxysilane, and ethylmethoxyphenyloxysilane;
[0063] Propyl hydrosilane compounds such as propyl dimethoxysilane, propyl methoxyethoxysilane, propyl diethoxysilane, propyl methoxypropoxysilane, propyl methoxypentyloxysilane, propyl ethoxypropoxysilane, propyl dipropoxysilane, propyl dipentyloxysilane, propyl diphenyloxysilane, and propyl methoxyphenyloxysilane; butylhydrosilane compounds such as butyldimethoxysilane, butylmethoxyethoxysilane, butyldiethoxysilane, butylmethoxypropoxysilane, butylmethoxypentyloxysilane, butylethoxypropoxysilane, butyldipropoxysilane, butyldipentyloxysilane, butyldiphenyloxysilane, and butylmethoxyphenyloxysilane;
[0064] Phenylhydrosilane compounds such as phenyldimethoxysilane, phenylmethoxyethoxysilane, phenyldiethoxysilane, phenylmethoxypropoxysilane, phenylmethoxypentyloxysilane, phenylethoxypropoxysilane, phenyldipropoxysilane, phenyldipentyloxysilane, phenyldiphenyloxysilane, and phenylmethoxyphenyloxysilane;
[0065] hydroxyphenyl hydrosilane compounds such as hydroxyphenyl dimethoxysilane, hydroxyphenyl methoxyethoxysilane, hydroxyphenyl diethoxysilane, hydroxyphenyl methoxypropoxysilane, hydroxyphenyl methoxypentyloxysilane, hydroxyphenyl ethoxypropoxysilane, hydroxyphenyl dipropoxysilane, hydroxyphenyl dipentyloxysilane, hydroxyphenyl diphenyloxysilane, and hydroxyphenyl methoxyphenyloxysilane;
[0066] naphthylhydrosilane compounds such as naphthyldimethoxysilane, naphthylmethoxyethoxysilane, naphthyldiethoxysilane, naphthylmethoxypropoxysilane, naphthylmethoxypentyloxysilane, naphthylethoxypropoxysilane, naphthyldipropoxysilane, naphthyldipentyloxysilane, naphthyldiphenyloxysilane, and naphthylmethoxyphenyloxysilane;
[0067] benzyl hydrosilane compounds such as benzyl dimethoxysilane, benzyl methoxyethoxysilane, benzyl diethoxysilane, benzyl methoxypropoxysilane, benzyl methoxypentyloxysilane, benzyl ethoxypropoxysilane, benzyl dipropoxysilane, benzyl dipentyloxysilane, benzyl diphenyloxysilane, and benzyl methoxyphenyloxysilane;
[0068] hydroxybenzyl hydrosilane compounds such as hydroxybenzyl dimethoxysilane, hydroxybenzyl methoxyethoxysilane, hydroxybenzyl diethoxysilane, hydroxybenzyl methoxypropoxysilane, hydroxybenzyl methoxypentyloxysilane, hydroxybenzyl ethoxypropoxysilane, hydroxybenzyl dipropoxysilane, hydroxybenzyl dipentyloxysilane, hydroxybenzyl diphenyloxysilane, and hydroxybenzyl methoxyphenyloxysilane;
[0069] dimethylsilane compounds such as dimethyldimethoxysilane, dimethylmethoxyethoxysilane, dimethylmethoxypropoxysilane, dimethyldiethoxysilane, dimethyldipentyloxysilane, dimethyldiphenyloxysilane, dimethylethoxypropoxysilane, and dimethyldipropoxysilane;
[0070] diethylsilane compounds such as diethyldimethoxysilane, diethylmethoxyethoxysilane, diethylmethoxypropoxysilane, diethyldiethoxysilane, diethyldipentyloxysilane, diethyldiphenyloxysilane, diethylethoxypropoxysilane, and diethyldipropoxysilane;
[0071] dipropoxysilane compounds such as dipropyldimethoxysilane, dipropylmethoxyethoxysilane, dipropylmethoxypropoxysilane, dipropyldiethoxysilane, dipropyldipentyloxysilane, dipropyldiphenyloxysilane, dipropylethoxypropoxysilane, and dipropyldipropoxysilane;
[0072] dibutylsilane compounds such as dibutyldimethoxysilane, dibutylmethoxyethoxysilane, dibutylmethoxypropoxysilane, dibutyldiethoxysilane, dibutyldipentyloxysilane, dibutyldiphenyloxysilane, dibutylethoxypropoxysilane, and dibutyldipropoxysilane;
[0073] diphenylsilane compounds such as diphenyldimethoxysilane, diphenylmethoxyethoxysilane, diphenylmethoxypropoxysilane, diphenyldiethoxysilane, diphenyldipentyloxysilane, diphenyldiphenyloxysilane, diphenylethoxypropoxysilane, and diphenyldipropoxysilane; di(hydroxyphenyl)silane compounds such as di(hydroxyphenyl)dimethoxysilane, di(hydroxyphenyl)methoxyethoxysilane, di(hydroxyphenyl)methoxypropoxysilane, di(hydroxyphenyl)diethoxysilane, di(hydroxyphenyl)dipentyloxysilane, di(hydroxyphenyl)diphenyloxysilane, di(hydroxyphenyl)ethoxypropoxysilane, and di(hydroxyphenyl)dipropoxysilane;
[0074] dinaphthylsilane compounds such as dinaphthyl dimethoxysilane, dinaphthyl methoxyethoxysilane, dinaphthyl methoxypropoxysilane, dinaphthyl diethoxysilane, dinaphthyl dipentyloxysilane, dinaphthyl diphenyloxysilane, dinaphthyl ethoxypropoxysilane, and dinaphthyl dipropoxysilane;
[0075] dibenzylsilane compounds such as dibenzyldimethoxysilane, dibenzylmethoxyethoxysilane, dibenzylmethoxypropoxysilane, dibenzyldiethoxysilane, dibenzyldipentyloxysilane, dibenzyldiphenyloxysilane, dibenzylethoxypropoxysilane, and dibenzyldipropoxysilane;
[0076] di(hydroxybenzyl)silane compounds such as di(hydroxybenzyl)dimethoxysilane, di(hydroxybenzyl)methoxyethoxysilane, di(hydroxybenzyl)methoxypropoxysilane, di(hydroxybenzyl)diethoxysilane, di(hydroxybenzyl)dipentyloxysilane, di(hydroxybenzyl)diphenyloxysilane, di(hydroxybenzyl)ethoxypropoxysilane, and di(hydroxybenzyl)dipropoxysilane;
[0077] methylethylsilane compounds such as methylethyldimethoxysilane, methylethylmethoxyethoxysilane, methylethylmethoxypropoxysilane, methylethyldiethoxysilane, methylethyldipentyloxysilane, methylethyldiphenyloxysilane, methylethylethoxypropoxysilane, and methylethyldipropoxysilane;
[0078] methylpropyl silane compounds such as methylpropyl dimethoxysilane, methylpropyl methoxyethoxysilane, methylpropyl methoxypropoxysilane, methylpropyl diethoxysilane, methylpropyl dipentyloxysilane, methylpropyl diphenyloxysilane, methylpropyl ethoxypropoxysilane, and methylpropyl dipropoxysilane;
[0079] methylbutylsilane compounds such as methylbutyldimethoxysilane, methylbutylmethoxyethoxysilane, methylbutylmethoxypropoxysilane, methylbutyldiethoxysilane, methylbutyldipentyloxysilane, methylbutyldiphenyloxysilane, methylbutylethoxypropoxysilane, and methylbutyldipropoxysilane;
[0080] Methyl(phenyl)silane compounds such as methyl(phenyl)dimethoxysilane, methyl(phenyl)methoxyethoxysilane, methyl(phenyl)methoxypropoxysilane, methyl(phenyl)diethoxysilane, methyl(phenyl)dipentyloxysilane, methyl(phenyl)diphenyloxysilane, methyl(phenyl)ethoxypropoxysilane, and methyl(phenyl)dipropoxysilane;
[0081] Methyl(hydroxyphenyl)silane compounds such as methyl(hydroxyphenyl)dimethoxysilane, methyl(hydroxyphenyl)methoxyethoxysilane, methyl(hydroxyphenyl)methoxypropoxysilane, methyl(hydroxyphenyl)diethoxysilane, methyl(hydroxyphenyl)dipentyloxysilane, methyl(hydroxyphenyl)diphenyloxysilane, methyl(hydroxyphenyl)ethoxypropoxysilane, and methyl(hydroxyphenyl)dipropoxysilane;
[0082] Methyl(naphthyl)silane compounds such as methyl(naphthyl)dimethoxysilane, methyl(naphthyl)methoxyethoxysilane, methyl(naphthyl)methoxypropoxysilane, methyl(naphthyl)diethoxysilane, methyl(naphthyl)dipentyloxysilane, methyl(naphthyl)diphenyloxysilane, methyl(naphthyl)ethoxypropoxysilane, and methyl(naphthyl)dipropoxysilane;
[0083] Methyl(benzyl)silane compounds such as methyl(benzyl)dimethoxysilane, methyl(benzyl)methoxyethoxysilane, methyl(benzyl)methoxypropoxysilane, methyl(benzyl)diethoxysilane, methyl(benzyl)dipentyloxysilane, methyl(benzyl)diphenyloxysilane, methyl(benzyl)ethoxypropoxysilane, and methyl(benzyl)dipropoxysilane;
[0084] methyl(hydroxybenzyl)silane compounds such as methyl(hydroxybenzyl)dimethoxysilane, methyl(hydroxybenzyl)methoxyethoxysilane, methyl(hydroxybenzyl)methoxypropoxysilane, methyl(hydroxybenzyl)diethoxysilane, methyl(hydroxybenzyl)dipentyloxysilane, methyl(hydroxybenzyl)diphenyloxysilane, methyl(hydroxybenzyl)ethoxypropoxysilane, and methyl(hydroxybenzyl)dipropoxysilane;
[0085] ethylpropyl silane compounds such as ethylpropyl dimethoxysilane, ethylpropyl methoxyethoxysilane, ethylpropyl methoxypropoxysilane, ethylpropyl diethoxysilane, ethylpropyl dipentyloxysilane, ethylpropyl diphenyloxysilane, ethylpropyl ethoxypropoxysilane, and ethylpropyl dipropoxysilane;
[0086] Ethylbutylsilane compounds such as ethylbutyldimethoxysilane, ethylbutylmethoxyethoxysilane, ethylbutylmethoxypropoxysilane, ethylbutyldiethoxysilane, ethylbutyldipentyloxysilane, ethylbutyldiphenyloxysilane, ethylbutylethoxypropoxysilane, and ethylbutyldipropoxysilane;
[0087] Ethyl(phenyl)silane compounds such as ethyl(phenyl)dimethoxysilane, ethyl(phenyl)methoxyethoxysilane, ethyl(phenyl)methoxypropoxysilane, ethyl(phenyl)diethoxysilane, ethyl(phenyl)dipentyloxysilane, ethyl(phenyl)diphenyloxysilane, ethyl(phenyl)ethoxypropoxysilane, and ethyl(phenyl)dipropoxysilane;
[0088] Ethyl(hydroxyphenyl)silane compounds such as ethyl(hydroxyphenyl)dimethoxysilane, ethyl(hydroxyphenyl)methoxyethoxysilane, ethyl(hydroxyphenyl)methoxypropoxysilane, ethyl(hydroxyphenyl)diethoxysilane, ethyl(hydroxyphenyl)dipentyloxysilane, ethyl(hydroxyphenyl)diphenyloxysilane, ethyl(hydroxyphenyl)ethoxypropoxysilane, and ethyl(hydroxyphenyl)dipropoxysilane;
[0089] Ethyl(naphthyl)silane compounds such as ethyl(naphthyl)dimethoxysilane, ethyl(naphthyl)methoxyethoxysilane, ethyl(naphthyl)methoxypropoxysilane, ethyl(naphthyl)diethoxysilane, ethyl(naphthyl)dipentyloxysilane, ethyl(naphthyl)diphenyloxysilane, ethyl(naphthyl)ethoxypropoxysilane, and ethyl(naphthyl)dipropoxysilane;
[0090] Ethyl(benzyl)silane compounds such as ethyl(benzyl)dimethoxysilane, ethyl(benzyl)methoxyethoxysilane, ethyl(benzyl)methoxypropoxysilane, ethyl(benzyl)diethoxysilane, ethyl(benzyl)dipentyloxysilane, ethyl(benzyl)diphenyloxysilane, ethyl(benzyl)ethoxypropoxysilane, and ethyl(benzyl)dipropoxysilane;
[0091] Ethyl(hydroxybenzyl)silane compounds such as ethyl(hydroxybenzyl)dimethoxysilane, ethyl(hydroxybenzyl)methoxyethoxysilane, ethyl(hydroxybenzyl)methoxypropoxysilane, ethyl(hydroxybenzyl)diethoxysilane, ethyl(hydroxybenzyl)dipentyloxysilane, ethyl(hydroxybenzyl)diphenyloxysilane, ethyl(hydroxybenzyl)ethoxypropoxysilane, and ethyl(hydroxybenzyl)dipropoxysilane;
[0092] Propylbutylsilane compounds such as propylbutyldimethoxysilane, propylbutylmethoxyethoxysilane, propylbutylmethoxypropoxysilane, propylbutyldiethoxysilane, propylbutyldipentyloxysilane, propylbutyldiphenyloxysilane, propylbutylethoxypropoxysilane, and propylbutyldipropoxysilane;
[0093] Propyl(phenyl)silane compounds such as propyl(phenyl)dimethoxysilane, propyl(phenyl)methoxyethoxysilane, propyl(phenyl)methoxypropoxysilane, propyl(phenyl)diethoxysilane, propyl(phenyl)dipentyloxysilane, propyl(phenyl)diphenyloxysilane, propyl(phenyl)ethoxypropoxysilane, and propyl(phenyl)dipropoxysilane;
[0094] Propyl(hydroxyphenyl)silane compounds such as propyl(hydroxyphenyl)dimethoxysilane, propyl(hydroxyphenyl)methoxyethoxysilane, propyl(hydroxyphenyl)methoxypropoxysilane, propyl(hydroxyphenyl)diethoxysilane, propyl(hydroxyphenyl)dipentyloxysilane, propyl(hydroxyphenyl)diphenyloxysilane, propyl(hydroxyphenyl)ethoxypropoxysilane, and propyl(hydroxyphenyl)dipropoxysilane;
[0095] Propyl(naphthyl)silane compounds such as propyl(naphthyl)dimethoxysilane, propyl(naphthyl)methoxyethoxysilane, propyl(naphthyl)methoxypropoxysilane, propyl(naphthyl)diethoxysilane, propyl(naphthyl)dipentyloxysilane, propyl(naphthyl)diphenyloxysilane, propyl(naphthyl)ethoxypropoxysilane, and propyl(naphthyl)dipropoxysilane;
[0096] Propyl(benzyl)silane compounds such as propyl(benzyl)dimethoxysilane, propyl(benzyl)methoxyethoxysilane, propyl(benzyl)methoxypropoxysilane, propyl(benzyl)diethoxysilane, propyl(benzyl)dipentyloxysilane, propyl(benzyl)diphenyloxysilane, propyl(benzyl)ethoxypropoxysilane, and propyl(benzyl)dipropoxysilane;
[0097] Examples of propyl(hydroxybenzyl)silane compounds include propyl(hydroxybenzyl)dimethoxysilane, propyl(hydroxybenzyl)methoxyethoxysilane, propyl(hydroxybenzyl)methoxypropoxysilane, propyl(hydroxybenzyl)diethoxysilane, propyl(hydroxybenzyl)dipentyloxysilane, propyl(hydroxybenzyl)diphenyloxysilane, propyl(hydroxybenzyl)ethoxypropoxysilane, and propyl(hydroxybenzyl)dipropoxysilane. The silane compound (b) may be used alone or in combination of two or more kinds.
[0098] The partial hydrolysis condensate of at least one silane compound (b) can be obtained by subjecting the silane compound (b) or a mixture of two or more kinds thereof to a hydrolysis condensation reaction by a known method. For example, a predetermined amount of water and, if necessary, an organic solvent are added to a monomer of tetramethoxysilane, and in the presence of a catalyst, the reaction is usually carried out at room temperature to 100°C while distilling off the by-product alcohol. This causes hydrolysis and condensation of tetramethoxysilane to proceed, producing a liquid tetramethoxysilane partial hydrolysis condensate (average degree of polymerization is usually about 2 to 8, mostly 3 to 7). The liquid tetramethoxysilane partial hydrolysis condensate can be, for example, CHO-(Si(OCH)-O) s It is represented by -CH3, and s represents the average degree of polymerization and is a number from 2 to 8. The degree of hydrolysis can be appropriately adjusted by the amount of water used. The liquid tetramethoxysilane partial hydrolysis condensate obtained as described above may be further subjected to hydrolysis condensation reaction. The method for further hydrolysis condensation reaction of the liquid tetramethoxysilane partial hydrolysis condensate is the same as the method for converting a primary reactant into a secondary reactant, which will be described later. In the case of a silane compound (b) other than tetramethoxysilane, a partial hydrolysis condensation product can be obtained in the same manner. A mixture of two or more silane compounds (b) may be used as a partial hydrolysis condensation product.
[0099] Examples of the catalyst include inorganic acids such as hydrochloric acid, acetic acid, nitric acid, formic acid, sulfuric acid, and phosphoric acid; organic acids such as formic acid, acetic acid, propionic acid, oxalic acid, paratoluenesulfonic acid, benzoic acid, phthalic acid, and maleic acid; alkali catalysts such as potassium hydroxide, sodium hydroxide, calcium hydroxide, and ammonia; organic metals, metal alkoxides, for example, organic tin compounds such as dibutyltin dilaurate, dibutyltin dioctiate, and dibutyltin diacetate; metal chelate compounds such as aluminum tris(acetylacetonate), titanium tetrakis(acetylacetonate), titanium bis(butoxy)bis(acetylacetonate), titanium bis(isopropoxy)bis(acetylacetonate), zirconium tetrakis(acetylacetonate), zirconium bis(butoxy)bis(acetylacetonate), and zirconium bis(isopropoxy)bis(acetylacetonate); boron compounds such as boric acid butoxide and boric acid. Among these, organic acids or metal chelate compounds are preferred for producing the secondary reaction product, and maleic acid or metal acetylacetonates are particularly preferred. The amount of the acid catalyst used is not particularly limited as long as it is an amount that can exert its catalytic function, but is usually selected from the range of about 0.001 to 10 parts by mass, and preferably 0.003 to 5 parts by mass, per 100 parts by mass of the silane compound (b).
[0100] From the viewpoint of reactivity, the component (B) is R 6 , R 7 , R 8 and R 9 is an alkyl group, i.e., it is preferable that the silane compound (b1) contains a tetraalkoxysilane or a partial hydrolyzed condensate thereof, it is more preferable that the silane compound (b1) contains a partial hydrolyzed condensate of a tetraalkoxysilane, and it is particularly preferable that the silane compound (b1) contains a partial hydrolyzed condensate of a tetramethoxysilane.
[0101] From the viewpoint of the appearance of the cured product, Mw of component (B) is preferably at least 500, more preferably at least 600. The upper limit of Mw of component (B) is, for example, 10,000. The Mw of component (B) is a value calculated as standard polystyrene as measured by gel permeation chromatography (GPC).
[0102] From the viewpoint of reactivity, component (B) is preferably a product (hereinafter also referred to as "secondary reactant") obtained by subjecting a partial hydrolysis condensation product of at least one silane compound (b) having an Mw of 300 to 3000 (hereinafter also referred to as "primary reactant") to a further hydrolysis condensation reaction in the presence of a catalyst. By using the secondary reaction product as component (B), the curability of the resin composition and the appearance of the cured product can be improved. The reason for this is not clear, but the following is thought to be the case. In the secondary reaction product, hydrolysis is promoted, so there are more silanol groups (Si-OH) than in the primary reaction product. The silanol group is Si-OR 5 It has higher reactivity than , so it has better curability. In addition, it promotes the condensation reaction, which increases the molecular weight and suppresses cracks, improving the appearance.
[0103] When the Mw of the primary reaction product is 300 or more, the appearance of the cured product is good, and when it is 3000 or less, the reactivity tends to be good. The Mw of the primary reaction product is preferably 400 to 2000, and more preferably 500 to 1000. As the silane compound (b) forming the primary reaction product, from the viewpoint of hardness of the cured product, the silane compound (b1) is preferable, a tetraalkoxysilane is more preferable, and tetramethoxysilane is even more preferable. As described above, the primary reaction product can be obtained by subjecting the silane compound (b) or a mixture of two or more kinds thereof to a hydrolysis and condensation reaction. Incidentally, commercially available primary reactants can also be used, such as MS51, MS53, MS57, and MS56S manufactured by Mitsubishi Chemical Corporation, and Ethyl Silicate 40, Ethyl Silicate 48, Methyl Silicate 51, Methyl Silicate 53A, and EMS-485 manufactured by Colcoat. A method for subjecting the primary reactant to further hydrolysis and condensation reaction in the presence of a catalyst to produce a secondary reactant includes a method of adding water, a catalyst, and a solvent to the primary reactant and stirring for one day or more at 25° C. Furthermore, the progress of the reaction can be promoted by heating the primary reactant, and in this case, for example, a method of stirring at 30° C. to 100° C. for one hour or more can be used.
[0104] From the empirical temperature and reaction time in the studies of the present inventors, the Mw of the secondary reaction product is preferably 400 to 50,000, more preferably 600 to 30,000, further preferably 800 to 10,000, particularly preferably 900 to 5,000, and most preferably 1,000 to 2,000.
[0105] In addition, since the reaction of the secondary reactant progresses over time, it is difficult to identify its structure and properties (e.g., radius, hydroxyl value, etc.) other than Mw by general analytical methods. Although Mw can be measured, the reactivity of the resin composition and the appearance of the cured product differ when the primary reactant is used as component (B) and when the secondary reactant is used. In other words, there are circumstances (impossible / unpractical circumstances) in which it is impossible or practical to directly identify the secondary reactant by its structure or properties. Therefore, it is more appropriate to define the secondary reactant as "a partial hydrolysis condensation product of at least one silane compound (b) having an Mw of 300 to 3000, which is further subjected to a hydrolysis condensation reaction in the presence of a catalyst."
[0106] <Initiator (C)> By including the initiator (C) in the present resin composition, the hydrolysis and condensation reaction of the component (B) and the group (1) is facilitated, and the curability of the present resin composition is improved. Examples of the initiator (C) include a photopolymerization initiator, a thermal polymerization initiator, a metal catalyst, and an acid catalyst.
[0107] Examples of the photopolymerization initiator include a photoradical polymerization initiator, a photoacid generator, and a photobase generator. Examples of the thermal polymerization initiator include a thermal radical polymerization initiator, a thermal acid generator, and a thermal base generator. Examples of the metal catalyst or acid catalyst include the same catalysts as those used in obtaining the partial hydrolysis condensation product of the silane compound (b). These may be used alone or in combination of two or more.
[0108] Among the above initiators (C), photopolymerization initiators are preferred. When the resin composition contains a photopolymerization initiator, the curing of the resin composition can be promoted by irradiation with active energy rays such as ultraviolet rays. When the resin composition is applied to a resin substrate and then cured by heat, the resin substrate may be deformed by heat. However, when the resin composition is cured by active energy rays, the deformation of the resin substrate by heat can be suppressed, so that the composition can be applied to resin substrates with low heat resistance. In addition, curing by active energy rays generally takes a shorter curing time than other curing methods such as heat curing and moisture curing, and therefore improved productivity can be expected.
[0109] As the photopolymerization initiator, at least one selected from the group consisting of a photoradical polymerization initiator, a photoacid generator, and a photobase generator is preferred, because it can initiate a hydrolysis and condensation reaction of component (B) and group (1) and can efficiently cure the present resin composition, at least one selected from the group consisting of a photoacid generator and a photobase generator is more preferred, and a photoacid generator is even more preferred.
[0110] Representative examples of the photoradical polymerization initiator (hereinafter also simply referred to as "photoinitiator") include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, and the like. acetophenones such as 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer, benzoins such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenone, o-benzoylbenzoyl Benzophenones such as methyl benzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, (4-benzoylbenzyl)trimethylammonium chloride; 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, Thioxanthones such as xanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride; and acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.However, the photoradical polymerization initiator is not limited to the exemplified compounds. The photoradical polymerization initiator may be used alone or in combination of two or more kinds.
[0111] Representative examples of photoacid generators include sulfonium salts (particularly triarylsulfonium salts) such as triarylsulfonium hexafluorophosphate (e.g., p-phenylthiophenyldiphenylsulfonium hexafluorophosphate, etc.) and triarylsulfonium hexafluoroantimonate; iodonium salts such as diaryliodonium hexafluorophosphate, diaryliodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, and iodonium [4-(4-methylphenyl-2-methylpropyl)phenyl]hexafluorophosphate. However, photoacid generators are not limited to the exemplified compounds. One type of photoacid generator may be used alone, or two or more types may be used in combination.
[0112] Representative examples of photobase generators include 1-(anthraquinone-2-yl)ethyl N-cyclohexylcarbamate, 9-anthrylmethyl N,N-diethylcarbamate, 9-anthrylmethyl piperidine-1-carboxylate, 9-anthrylmethyl N,N-dicyclohexylcarbamate, 1-(anthraquinone-2-yl)ethyl N,N-dicyclohexylcarbamate, 1-(anthraquinone-2-yl)ethyl imidazole-1-carboxylate, cyclohexylammonium 2-(3-benzoylphenyl)propionate, (E)-N-cyclohexyl-3-(2-hydroxyphenyl)acrylamide, dicyclohexylammonium Examples of the photobase generator include guanidinium 2-(3-benzoylphenyl)propionate, 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidinium n-butyltriphenylborate, 1,2-diisopropyl 3-[bis(dimethylamino)methylene]guanidinium 2-(3-benzoylphenyl)propionate, 4-hydroxypiperidine-1-carboxylate (2-nitrophenyl)methyl, 4-(methacryloyloxy)piperidine-1-carboxylate (2-nitrophenyl)methyl, guanidinium 2-(3-benzoylphenyl)propionate, and (E)-1-piperidino-3-(2-hydroxyphenyl)-2-propen-1-one. However, the photobase generator is not limited to the exemplified compounds. The photobase generator may be used alone or in combination of two or more.
[0113] <Diluent> When the present resin composition contains a diluent, the coating workability when the present resin composition is applied to a substrate, the smoothness and uniformity of the formed coating film and the cured film, and the adhesion of the cured film to the substrate are improved. The diluent may be water or an organic solvent, with the organic solvent being preferred. When the component (B) is a hydrolysis condensation product of the silane compound (b), the diluent may contain water blended for subjecting the silane compound (b) to a hydrolysis condensation reaction.
[0114] Examples of the organic solvent include alcohol-based solvents, glycol-based solvents, hydrocarbon-based solvents, ester-based solvents, ketone-based solvents, and ether-based solvents.
[0115] Examples of the alcohol-based solvent include methanol, ethanol, isopropyl alcohol, n-butanol, isobutanol, octanol, n-propyl alcohol, and acetylacetone alcohol. Examples of glycol solvents include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-propyl ether, ethylene glycol mono n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monomethyl ether acetate.
[0116] Examples of the hydrocarbon solvent include benzene, kerosene, toluene, and xylene. Examples of the ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, and ethyl acetoacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, and acetylacetone. Examples of the ether solvent include ethyl ether, butyl ether, methyl cellosolve, ethyl cellosolve, dioxane, furan, and tetrahydrofuran. The organic solvents may be used alone or in combination of two or more kinds.
[0117] As the diluent, an alcohol-based solvent is preferable, and methanol, ethanol, isopropanol, or n-propanol is more preferable, because it is easy to handle, has good storage stability in liquid form, and the properties of the resulting cured product are excellent.
[0118] <Other ingredients> Examples of other components include polymers other than the copolymer (A), ultraviolet absorbers, light stabilizers, silane coupling agents, inorganic fine particles, antioxidants, anti-yellowing agents, bluing agents, pigments, leveling agents, defoamers, thickeners, anti-settling agents, antistatic agents, and anti-fogging agents.
[0119] <Content of each ingredient> The content of copolymer (A) is preferably 1 to 95 mass%, more preferably 10 to 90 mass%, further preferably 20 to 85 mass%, particularly preferably 25 to 85 mass%, and most preferably 30 to 70 mass%, based on 100 mass% of the total non-volatile components in the resin composition. If the content of copolymer (A) is equal to or more than the lower limit, the cured product will have better water slipping property and appearance, and if it is equal to or less than the upper limit, the cured product will have better appearance and strength. The non-volatile components refer to the components excluding organic solvents.
[0120] The content of component (B) is preferably 1 to 90 mass%, more preferably 5 to 80 mass%, further preferably 10 to 75 mass%, particularly preferably 20 to 70 mass%, and most preferably 30 to 65 mass%, based on 100 mass% of the total non-volatile components in the resin composition. If the content of component (B) is equal to or more than the lower limit, the strength of the cured product will be superior, and if it is equal to or less than the upper limit, the appearance of the cured product will be superior.
[0121] The content of the initiator (C) is preferably 0.01 to 10 mass%, more preferably 0.05 to 9 mass%, further preferably 0.1 to 8 mass%, particularly preferably 0.2 to 5 mass%, and most preferably 0.2 to 3 mass%, based on 100 mass% of the total non-volatile components in the resin composition. If the content of the initiator (C) is equal to or more than the lower limit, the curability (reactivity) of the resin composition and the productivity of the cured product are superior, and if it is equal to or less than the upper limit, the water slipping property of the cured product is superior.
[0122] When the present resin composition contains a diluent, the concentration of the non-volatile components in the present resin composition is not particularly limited as long as it is a concentration suitable for the coating method. The lower the concentration of the non-volatile components, the better the smoothness and uniformity of the coating film formed and its cured film (cured product layer), and the better the adhesion between the substrate and the cured film, while the higher the concentration of the non-volatile components, the better the sagging suppression effect when the present resin composition is applied to the substrate.
[0123] The concentration of the non-volatile components in the entire resin composition is not particularly limited, but is preferably 80% by mass or less, more preferably 0.1 to 60% by mass, even more preferably 1 to 40% by mass, particularly preferably 1 to 30% by mass, and most preferably 1 to 20% by mass. By using the non-volatile components in the above range, a resin composition with excellent coatability can be obtained.
[0124] The resin composition is spray-coated on a substrate, and the cured film (initial cured film) is formed. The surface of the cured film has a sliding angle of 20 μL of water at 23° C. of preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the water sliding angle, and it is, for example, 1° or more. If the water sliding angle of the initial cured film is the above upper limit or less, raindrops or snow attached to the surface can slide off easily.
[0125] The sliding angle is measured while the inclination angle is changed intermittently by 1°. Details are as described in the examples below. Conventionally, the sliding angle is often measured while the inclination angle is changed continuously. The sliding angle measured while the inclination angle is changed intermittently by 1° tends to be larger than the sliding angle measured while the inclination angle is changed continuously.
[0126] The sliding angle can be adjusted by the content and type of polyalkylsiloxane unit in the resin composition. Specifically, the content of copolymer (A) is increased, or the proportion of silicone macromonomer (X) copolymerized in copolymer (A) is increased, or a silicone macromonomer (X) containing a longer chain polyalkylsiloxane unit is selected, and the initial water sliding angle of the cured film tends to be smaller.
[0127] Furthermore, the sliding angle after the durability test is particularly important in a wide range of applications, and the lower the sliding angle, the more preferable it is, and the less change therefrom from the initial state, the more preferable it is. After forming a cured film as described above and carrying out a durability test for 96 hours under conditions of 50°C and 99% RH or more, the sliding angle of 20 μL of water at 23°C on the surface of the cured film (cured film after durability test) is preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the sliding angle of water, and it is, for example, 1° or more.
[0128] The change in the water sliding angle of the cured film after the durability test from the initial water sliding angle (water sliding angle of the cured film after the durability test - water sliding angle of the initial cured film) is preferably 40° or less, more preferably 30° or less, even more preferably 20° or less, and most preferably 15° or less. There is no particular lower limit, but it is preferably 0°. By setting it in this range, it is possible to achieve the same level of performance as the initial performance over a long period of time, making it easier to design products.
[0129] The sliding angle after the weather resistance test is particularly important in a wide range of applications, and the lower the sliding angle, the better. Also, the less change there is from the initial state, the better. A hardened film was formed as described above, and the rain was 12 minutes out of 60 minutes, and the irradiation intensity was 180 W / m 2 (300-400 nm), the sliding angle of 20 μL of water at 23° C. on the surface of the cured film (cured film after durability test) after carrying out a weather resistance test for 500 hours under the conditions of a black panel temperature of 63° C., a temperature inside the tank of 50° C., and a humidity inside the tank of 50% is preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the sliding angle of water, and it is, for example, 1° or more.
[0130] The change in the water sliding angle of the cured film after the weather resistance test from the initial water sliding angle (water sliding angle of the cured film after the weather resistance test - water sliding angle of the initial cured film) is preferably 40° or less, more preferably 30° or less, even more preferably 20° or less, and most preferably 15° or less. There is no particular lower limit, but it is preferably 0°. By setting it in this range, it is possible to achieve the same level of performance as the initial performance over a long period of time, making it easier to design products.
[0131] <Method of producing resin composition> The present resin composition can be produced by mixing the copolymer (A), the component (B), and, if necessary, the initiator (C), a diluent, and other components. When the diluent contains water, the water may be added during the preparation of the hydrolysis condensate of the silane compound (b), or during the production of the present resin composition, or may be added both during the preparation of the hydrolysis condensate of the silane compound (b) and during the production of the present resin composition.
[0132] The present resin composition described above contains the copolymer (A), the component (B) and the initiator (C), and therefore can form a cured product that is excellent in appearance, water slippage, weather resistance and durability.
[0133] This resin composition can be used for sensing component applications such as surface materials for components through which electromagnetic waves of sensing components (millimeter wave radar, LiDAR, etc.) pass; various automobile lamp lenses (vehicle lighting fixtures), hard coating agents for resin glazing, road signs, traffic signals, camera lenses, 5G-related components, antennas, solar panels, window glass, resin glass, automotive glass, etc. Among the above applications, the present resin composition is preferably used as a sensing material. For example, when the surface material of an emblem or a front grille located in front of a millimeter wave radar or LiDAR in a vehicle is made of a cured product of the present resin composition, even if raindrops or snow adhere to the outermost surface of the emblem or the like, they slide off easily, and the electromagnetic waves of the millimeter wave radar or LiDAR can be prevented from being attenuated or scattered by raindrops or snow.
[0134] [Cured product] A cured product according to one embodiment of the present invention (hereinafter also referred to as the "present cured product") is a cured product of the present resin composition.
[0135] The present cured product can be obtained by curing the present resin composition. Examples of the curing method include a method of irradiating the present resin composition with active energy rays, a method of curing by heating, and a method of curing by utilizing moisture in the air. From the viewpoints of the temperature applied to the substrate and productivity, the method of irradiating the present resin composition with active energy rays is preferred.
[0136] Examples of the active energy ray include ultraviolet rays, electron beams, etc. Ultraviolet rays are preferred because they are easily available and have excellent polymerizability. When the resin composition is cured by ultraviolet irradiation, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a metal halide lamp, a UV-LED, a low pressure mercury lamp, a xenon excimer lamp, etc. can be used as the light source. From the viewpoint of productivity, it is preferable to use a light source that shows a maximum irradiation intensity at a wavelength of 150 to 420 nm. In addition, the cumulative irradiation amount of ultraviolet rays is 50 to 3000 mJ / cm. 2 is preferable, and 100 to 2000 mJ / cm 2 is more preferred.
[0137] The active energy rays may be irradiated in an air atmosphere or in an inert gas atmosphere such as nitrogen or argon.
[0138] The time for irradiating the active energy rays is preferably 1 minute or less, more preferably 30 seconds or less, and even more preferably 15 seconds or less, in terms of the appearance and strength of the cured product. There is no particular lower limit, but it is, for example, 0.1 seconds. The method of curing by irradiating the active energy rays can cure in a shorter time than the method of thermal curing, and is therefore a preferred embodiment in terms of productivity and cost.
[0139] When the resin composition contains a diluent, the resin composition may be subjected to a heat treatment in order to remove the diluent before being irradiated with active energy rays. This heat treatment can be performed by irradiation with a near-infrared lamp, circulation of hot air, or the like.
[0140] Furthermore, the present resin composition may be subjected to a heat treatment after being irradiated with active energy rays. This heat treatment can be performed by irradiation with a near-infrared lamp, circulation of hot air, etc. The cured product obtained by the heat treatment after curing by irradiation with active energy rays has a higher condensation reaction rate than that obtained without the heat treatment, and therefore tends to have excellent hardness and durability.
[0141] The sliding angle of 20 μL of water at 23° C. on the surface of the cured product (initial cured product) formed as described above is preferably lower, and is preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the sliding angle of water, and it is 0° or more. If the sliding angle of water is equal to or less than the above upper limit, raindrops or snow adhering to the surface slide off easily.
[0142] Furthermore, the water sliding angle after the durability test is particularly important in the development of a wide range of applications, and the lower the angle the better, and the less change there is from the initial state the better. After forming a cured product as described above and carrying out a durability test for 96 hours under conditions of 50°C and 99% RH or more, the sliding angle of 20 μL of water at 23°C on the surface of the cured product (cured product after durability test) is preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the sliding angle of water, and it is, for example, 1° or more.
[0143] The change in the water sliding angle of the cured product after the durability test from the initial water sliding angle (water sliding angle of the cured product after the durability test - initial water sliding angle of the cured product) is preferably 40° or less, more preferably 30° or less, even more preferably 20° or less, and most preferably 15° or less. There is no particular lower limit, but it is preferably -40°. By setting it in this range, it is possible to achieve performance equivalent to that of the initial state over a long period of time, making it easier to design products.
[0144] The present cured product described above is a cured product of a resin composition containing the copolymer (A) and the component (B), and therefore has excellent productivity, appearance, water slipping property and durability.
[0145] The present cured product can be used for sensing component applications such as surface materials for components through which electromagnetic waves of sensing components (millimeter wave radar, LiDAR, etc.) pass, hard coats for various lamp lenses (vehicle lighting fixtures) and resin glazing in automobiles, road signs, traffic signals, camera lenses, 5G-related components, antennas, solar panels, window glass, resin glass, automotive glass, etc. Of the above applications of the present cured product, sensing component applications are preferred.
[0146] [Method of manufacturing the cured product] The cured product can be produced, for example, by applying a curable composition containing the copolymer (A) and at least one silane compound (b) or a component (B) consisting of a partial hydrolysis condensate thereof onto a substrate and curing the composition (cured product formation process). After the cured product-forming step, the formed cured product may be peeled off from the substrate, if necessary.
[0147] <Curable composition> The curable composition comprises a copolymer (A) and a component (B). The curable composition typically includes a diluent. The curable composition preferably contains an initiator (C). The curable composition may contain other components in addition to those described above, as necessary. The copolymer (A), the initiator (C) and other components are as described above.
[0148] (Component (B)) Component (B) comprises at least one silane compound (b) or a partial hydrolysis condensate thereof. The silane compound (b) is as described above.
[0149] The partial hydrolysis condensate of at least one silane compound (b) can be obtained by subjecting the silane compound (b) or a mixture of two or more kinds thereof to a hydrolysis condensation reaction by a known method. For example, a predetermined amount of water and, if necessary, an organic solvent are added to a monomer of tetramethoxysilane, and in the presence of a catalyst, the reaction is usually carried out at room temperature to 100°C while distilling off the by-product alcohol. This causes hydrolysis and condensation of tetramethoxysilane to proceed, producing a liquid tetramethoxysilane partial hydrolysis condensate (average degree of polymerization is usually about 2 to 8, mostly 3 to 7). The liquid tetramethoxysilane partial hydrolysis condensate can be, for example, CHO-(Si(OCH)-O) s It is represented by -CH3, and s represents the average degree of polymerization and is a number from 2 to 8. The degree of hydrolysis can be appropriately adjusted by the amount of water used. The liquid tetramethoxysilane partial hydrolysis condensate obtained as described above may be further subjected to hydrolysis condensation reaction. The method for further hydrolysis condensation reaction of the liquid tetramethoxysilane partial hydrolysis condensate is the same as the method for converting a primary reactant into a secondary reactant, which will be described later. In the case of a silane compound (b) other than tetramethoxysilane, a partial hydrolysis condensation product can be obtained in the same manner. A mixture of two or more silane compounds (b) may be used as a partial hydrolysis condensation product.
[0150] Examples of the catalyst include inorganic acids such as hydrochloric acid, acetic acid, nitric acid, formic acid, sulfuric acid, and phosphoric acid; organic acids such as formic acid, acetic acid, propionic acid, oxalic acid, paratoluenesulfonic acid, benzoic acid, phthalic acid, and maleic acid; alkali catalysts such as potassium hydroxide, sodium hydroxide, calcium hydroxide, and ammonia; organic metals, metal alkoxides, organic tin compounds such as dibutyltin dilaurate, dibutyltin dioctiate, and dibutyltin diacetate; aluminum tris(acetylacetonate), titanium tetrakis(acetylacetonate), titanium bis(butoxy)bis(acetylacetonate), titanium bis(isopropoxy)bis(acetylacetonate), zirconium tetrakis(acetylacetonate), zirconium bis(butoxy)bis(acetylacetonate), and zirconium. Examples of the metal chelate compounds include bis(isopropoxy)bis(acetylacetonate), and boron compounds such as boric acid butoxide and boric acid. The amount of the acid catalyst used is not particularly limited as long as it is an amount that can exert its catalytic function, but is usually selected from the range of about 0.001 to 10 parts by mass, and preferably 0.003 to 5 parts by mass, per 100 parts by mass of the silane compound (b).
[0151] From the viewpoint of hardness of the cured product, the component (B) is R 6 , R 7 , R 8 and R 9 is an alkyl group, i.e., a tetraalkoxysilane or a partial hydrolysis condensate thereof. From the viewpoint of the water sliding angle, a partial hydrolysis condensate of a tetraalkoxysilane is more preferable, and a partial hydrolysis condensate of tetramethoxysilane is particularly preferable.
[0152] From the viewpoint of appearance, Mw of component (B) is preferably at least 500, more preferably at least 600. The upper limit of Mw of component (B) is, for example, 10,000. The Mw of component (B) is a value calculated as standard polystyrene as measured by gel permeation chromatography (GPC).
[0153] From the viewpoint of reactivity, component (B) is preferably a product (hereinafter also referred to as "secondary reactant") obtained by subjecting a partial hydrolysis condensation product of at least one silane compound (b) having an Mw of 300 to 3000 (hereinafter also referred to as "primary reactant") to a hydrolysis condensation reaction in the presence of a catalyst. By using the secondary reaction product as component (B), the storage stability of the curable composition is adequately maintained while the curability and appearance of the curable composition are excellent. The reason for this is not clear, but the following is thought to be the case. In the secondary reaction product, hydrolysis is accelerated, so that silanol groups (Si-OH) can be present in a large amount and in a stable manner compared to the primary reaction product. The silanol group is Si-OR 5 It has higher reactivity than , so it has better curability. In addition, it promotes the condensation reaction, which increases the molecular weight and suppresses cracks, improving the appearance.
[0154] When the Mw of the primary reaction product is 300 or more, the appearance of the cured product is good, and when it is 3000 or less, the reactivity tends to be good. The Mw of the primary reaction product is preferably 400 to 2000, and more preferably 500 to 1000. As the silane compound (b) forming the primary reaction product, from the viewpoint of the hardness of the cured layer, the silane compound (b1) is preferable, tetraalkoxysilane is more preferable, and tetramethoxysilane is further preferable. As described above, the primary reaction product can be obtained by subjecting the silane compound (b) or a mixture of two or more kinds thereof to a hydrolysis and condensation reaction. Incidentally, commercially available primary reactants can also be used, such as MS51, MS53, MS57, and MS56S manufactured by Mitsubishi Chemical Corporation, and Ethyl Silicate 40, Ethyl Silicate 48, Methyl Silicate 51, Methyl Silicate 53A, and EMS-485 manufactured by Colcoat. A method for subjecting the primary reactant to a hydrolysis and condensation reaction in the presence of a catalyst includes adding water, a catalyst, and a solvent to the primary reactant and stirring for one day or more at 25° C. Furthermore, the progress of the reaction can be promoted by heating the primary reactant, and in this case, for example, a method of stirring at 30° C. to 100° C. for one hour or more can be used. From the empirical temperature and reaction time in the studies of the present inventors, the Mw of the secondary reaction product is preferably 400 to 50,000, more preferably 600 to 30,000, further preferably 800 to 10,000, particularly preferably 900 to 5,000, and most preferably 1,000 to 2,000.
[0155] In addition, since the reaction of the secondary reactant progresses over time, it is difficult to identify its structure and properties (e.g., radius, hydroxyl value, etc.) other than Mw by general analytical methods. Although Mw can be measured, the reactivity of the curable composition and the appearance of the cured product differ when the primary reactant is used as component (B) and when the secondary reactant is used. In other words, there are circumstances (impossible / unpractical circumstances) in which it is impossible or practical to directly identify the secondary reactant by its structure or properties. Therefore, it is more appropriate to define the secondary reactant as "a partial hydrolysis condensation product of at least one silane compound (b) having an Mw of 300 to 3000, which is subjected to a hydrolysis condensation reaction in the presence of a catalyst."
[0156] (Diluent) When the curable composition contains a diluent, the coating workability when coating the curable composition, the smoothness and uniformity of the cured product formed, and the adhesion between the substrate and the cured product are improved. The diluent may be water or an organic solvent, with the organic solvent being preferred. Examples of the organic solvent include alcohol-based solvents, glycol-based solvents, hydrocarbon-based solvents, ester-based solvents, ketone-based solvents, and ether-based solvents.
[0157] Examples of the alcohol-based solvent include methanol, ethanol, isopropyl alcohol, n-butanol, isobutanol, octanol, n-propyl alcohol, and acetylacetone alcohol. Examples of glycol solvents include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-propyl ether, ethylene glycol mono n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monomethyl ether acetate.
[0158] Examples of the hydrocarbon solvent include benzene, kerosene, toluene, and xylene. Examples of the ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, and ethyl acetoacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, and acetylacetone. Examples of the ether solvent include ethyl ether, butyl ether, methyl cellosolve, ethyl cellosolve, dioxane, furan, and tetrahydrofuran. The organic solvents may be used alone or in combination of two or more kinds.
[0159] As the diluent, an alcohol-based solvent is preferable, and methanol, ethanol, isopropanol or n-propanol is more preferable, because they are easy to handle, have good storage stability in liquid form, and give a cured product with excellent properties. When the component (B) is a hydrolysis condensation product of the silane compound (b), the diluent may contain water blended for subjecting the silane compound (b) to a hydrolysis condensation reaction.
[0160] In the curable composition, the content of copolymer (A) is preferably 1 to 95 mass%, more preferably 10 to 90 mass%, further preferably 20 to 85 mass%, particularly preferably 25 to 85 mass%, and most preferably 30 to 65 mass%, based on 100 mass% of the nonvolatile components in the curable composition. When the content of copolymer (A) is equal to or more than the lower limit, the cured product has better water slipping property and appearance, and when the content is equal to or less than the upper limit, the cured product has better appearance and strength.
[0161] The content of component (B) is preferably 1 to 90 mass%, more preferably 5 to 80 mass%, further preferably 10 to 75 mass%, particularly preferably 18 to 70 mass%, and most preferably 30 to 65 mass%, based on 100 mass% of the nonvolatile components in the curable composition. When the content of component (B) is equal to or more than the lower limit, the durability and strength of the cured product are superior, and when it is equal to or less than the upper limit, the appearance of the cured product is superior.
[0162] The content of the initiator (C) is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on 100% by mass of the non-volatile components in the curable composition. There is no particular restriction on the lower limit, but in the case of a cured product cured by irradiation with active energy rays, the content is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.2% by mass or more.
[0163] The concentration of the non-volatile components in the entire curable composition is not particularly limited, but is preferably 80% by mass or less, more preferably 0.1 to 60% by mass, even more preferably 1 to 40% by mass, particularly preferably 1 to 30% by mass, and most preferably 1 to 20% by mass. By using the non-volatile components in the above range, a composition with excellent coatability can be obtained. The non-volatile components refer to components excluding the diluent.
[0164] The content of the other components is not particularly limited, but may be, for example, about 0 to 30% by mass relative to 100% by mass of the non-volatile components in the curable composition. However, when used in applications where water sliding is particularly important, it is preferable to increase the content of the compound containing silicon atoms as much as possible from the viewpoint of the sliding angle, and it is preferable not to contain other components.
[0165] The curable composition can be prepared by mixing the copolymer (A), the component (B), and, if necessary, a diluent, an initiator (C), and other components. When the diluent contains water, the water may be added during the preparation of the hydrolysis condensate of the silane compound (b), or during the production of the curable composition, or may be added both during the preparation of the hydrolysis condensate of the silane compound (b) and during the production of the composition.
[0166] <Cured product formation process> The curable composition can be applied by any known method, such as brush coating, gravure coating, die coating, bar coating, spray coating, flow coating, dip coating, spin coating, or curtain coating.
[0167] Examples of the curing method include a method of irradiating the curable composition with active energy rays, a method of curing by heating, a method of curing by utilizing moisture in the air, etc. In cases where the substrate is a resin substrate or the like that is weak against heat, or when it is desired to improve the hardness or productivity of the cured product, the method of irradiating the curable composition with active energy rays may be preferable.
[0168] When the curable composition is cured by heating, examples of the heating method include irradiation with a near-infrared lamp, circulation of hot air, etc. Heating conditions are preferably heating at 60° C. to 200° C. for 10 minutes to 3 hours, and more preferably heating at 80° C. to 150° C. for 30 minutes to 2 hours. The curable composition may be heated in an air atmosphere or in an inert gas atmosphere such as nitrogen or argon.
[0169] When the curable composition is cured by irradiation with active energy rays, examples of the active energy rays include ultraviolet rays, electron beams, etc. From the viewpoints of ease of introducing equipment and cost, ultraviolet rays are preferred. When the curable composition is cured by ultraviolet irradiation, the light source may be a high pressure mercury lamp, an ultra-high pressure mercury lamp, a metal halide lamp, a UV-LED, a low pressure mercury lamp, a xenon excimer lamp, etc. From the viewpoint of productivity, it is preferable to use a light source that shows a maximum irradiation intensity at a wavelength of 150 to 420 nm. In addition, the cumulative irradiation amount of ultraviolet light is 50 to 3000 mJ / cm. 2 is preferable, and 100 to 2000 mJ / cm 2 is more preferred. The active energy rays may be irradiated in an air atmosphere or in an inert gas atmosphere such as nitrogen or argon.
[0170] When the curable composition contains a diluent, the curable composition may be subjected to a heat treatment in order to remove the diluent after coating and before irradiating the curable composition with active energy rays for drying. This heat treatment can be performed by irradiation with a near-infrared lamp, circulation of hot air, or the like.
[0171] The cured product obtained by irradiating active energy rays after heat treatment is less likely to have residual diluent inside the cured product, and therefore tends to have improved adhesion over a long period outdoors compared to a product not subjected to heat treatment. From the viewpoint of the appearance and adhesion of the cured product, the conditions of the heat treatment for drying are that the surface temperature of the substrate (hereinafter referred to as heating temperature) is preferably 40 to 90°C, more preferably 50 to 70°C, and the drying time is preferably 60 to 180 seconds, more preferably 90 to 150 seconds.
[0172] The curable composition may be subjected to a heat treatment after being irradiated with active energy rays. This heat treatment can be performed by irradiation with a near-infrared lamp, circulation of hot air, etc. The cured product obtained by the heat treatment after curing by irradiation with active energy rays has a higher condensation reaction rate than that obtained without the heat treatment, and therefore tends to have excellent hardness and durability.
[0173] The contact angle of 1 μL of distilled water at 23° C. on the surface of the initial cured layer (hereinafter also referred to as the “water contact angle”) is preferably 70° or more, more preferably 80° or more, even more preferably 90° or more, particularly preferably 95° or more, and most preferably 100° or more. If the contact angle is equal to or greater than the lower limit, the antifouling properties are more excellent. There is no particular restriction on the upper limit, but it is preferably 150°.
[0174] The contact angle of water can be adjusted by the content of copolymer (A), the content of silicone macromonomer (X) in copolymer (A), etc. Specifically, the contact angle tends to increase when the content of copolymer (A) is increased or the content of silicone macromonomer (X) in copolymer (A) is increased.
[0175] The thickness of the cured product formed on the substrate is preferably 10 nm to 4 μm, more preferably 20 nm to 3 μm. If the thickness of the cured product is equal to or greater than the lower limit, the cured product has better water sliding properties and scratch resistance, whereas if the thickness is equal to or less than the upper limit, the cured product tends not to crack.
[0176] The cured product described above contains the copolymer (A) and the component (B), and therefore has excellent water slipping properties, appearance and durability.
[0177] The cured product can be used for sensing component applications such as components through which electromagnetic waves of sensing components (millimeter wave radar, LiDAR, etc.) pass, various lamp lenses (vehicle lighting devices) for automobiles, resin glazing, road signs, traffic signals, camera lenses, 5G-related components, antennas, solar panels, window glass, resin glass, automotive glass, etc. Among the above applications of the cured product, sensing component applications are preferred.
[0178] [Laminate] A laminate according to one embodiment of the present invention (hereinafter also referred to as "the laminate") has a substrate and a layer made of a cured product (hereinafter also referred to as "cured product layer"). The cured product layer is preferably located as the outermost layer of the present laminate. A primer layer may be provided between the substrate and the cured material layer.
[0179] When a resin substrate is used as the substrate, the laminate preferably contains at least one selected from the group consisting of an ultraviolet absorber and a light stabilizer. By containing an ultraviolet absorber or a light stabilizer, the laminate is prevented from being deteriorated by ultraviolet rays or the like, and the laminate itself or the member underlying the laminate is improved in weather resistance and durability. The ultraviolet absorber and the light stabilizer will be described in detail later. The ultraviolet absorber and the light stabilizer may be contained in any layer of the laminate. However, from the viewpoint of protecting the member, easiness of curing the cured layer of the laminate, and maintenance of water slip performance, the ultraviolet absorber and the light stabilizer are preferably contained in the base material or the primer layer, and more preferably contained in the primer layer in consideration of ease of designing the entire laminate. In the laminate, it is preferable that the light stabilizer is contained in the substrate or the primer layer, and it is more preferable that the light stabilizer is contained in the primer layer in consideration of ease of designing the entire laminate. The light stabilizer can capture radicals generated by light, so that it can improve resistance to light (particularly ultraviolet light). In particular, it is preferable that an ultraviolet absorber is contained together with the light stabilizer.
[0180] The content of the ultraviolet absorber or light stabilizer depends on the layer used in the laminate and the film thickness of the layer, so it cannot be generalized. For example, when the ultraviolet absorber or light stabilizer is contained in the substrate, the content of each of the ultraviolet absorber and light stabilizer is usually 10% by mass or less, preferably 0.01 to 5% by mass, and more preferably 0.1 to 3% by mass, based on the total mass of the substrate. When the ultraviolet absorber or light stabilizer is contained in the primer layer, the content of each of the ultraviolet absorber and light stabilizer is preferably 30% by mass or less, more preferably 0.01 to 20% by mass, even more preferably 0.1 to 15% by mass, and particularly preferably 0.3 to 15% by mass, based on the total mass of the primer layer. By using within the above range, it is possible to improve the weather resistance of the substrate or member while maintaining other properties, and to prevent deterioration.
[0181] [Base material] Examples of the substrate include glass substrates; metal substrates such as zinc-plated steel sheets, zinc alloy-plated steel sheets, stainless steel sheets, and tin-plated steel sheets; and resin substrates such as polymethyl methacrylate resins, polycarbonate resins, polyester resins, polystyrene resins, ABS resins, AS resins, polyamide resins, polyarylate resins, polyurethane resins, polyvinyl resins, triacetyl cellulose, polymethacrylimide resins, and polyallyl diglycol carbonate resins. Considering that the laminate is used for various members, the resin constituting the resin substrate is preferably glass, polycarbonate resins, polyester resins, triacetyl cellulose, polyurethane resins, or polyvinyl resins, and more preferably polycarbonate resins or polyester resins, from the viewpoints of transparency and mechanical strength. In addition to the resin, the resin substrate may contain additives such as ultraviolet absorbers, light stabilizers, plasticizers, antistatic agents, flame retardants, reinforcing materials, fillers, colorants, lubricants, foaming agents, lubricants, and curing catalysts. If necessary, a primer layer may be present on the substrate to improve adhesion, and a functional layer such as an adhesive layer, an anti-fogging layer, or an anti-reflection layer may be present on the side opposite to the side on which the cured product layer of the substrate is present. A heater may be mounted on the side opposite to the outermost surface of the laminate or inside the laminate.
[0182] [Primer layer] The primer layer contributes to improving the adhesion between the substrate and the cured layer and the coatability when laminating the cured layer. In the course of further investigation, it was found that in the past, when a resin substrate was used, the difference in the components of the cured layer was large, and therefore adhesion (adhesion between the substrate and the cured layer) was likely to be poor. Therefore, when a resin substrate is used as the substrate, it was found that the adhesion problem can be solved by providing a primer layer between the substrate and the cured layer in order to achieve both adhesion to the substrate and adhesion to the cured layer. The primer layer typically contains a resin component. The primer layer preferably contains at least one selected from the group consisting of an ultraviolet absorber and a light stabilizer. The primer layer may contain additives other than the ultraviolet absorber and the light stabilizer, if necessary, within the range not impairing the effects of the present invention.
[0183] <Resin component> Examples of the resin component include acrylic resin, polyester resin, urethane resin, vinyl resin, etc. Among these, from the viewpoint of improving adhesion, acrylic resin or urethane resin is preferable. These resin components may be used alone or in combination of two or more. In addition, the resin component may be a non-curable resin or a compound derived from a curable compound (monomer, oligomer, etc.). Examples of the compound derived from a curable compound include a cured product of the curable compound. A compound derived from a curable compound is preferred from the viewpoint of further improving adhesion to the cured layer and improving the durability of the cured layer. A primer layer containing a compound derived from a curable compound is formed by including a curable compound in a primer that forms a primer layer, applying the primer onto a substrate, and curing the curable compound on the substrate. Such a primer layer has excellent adhesion to the substrate and improves adhesion between the substrate and the cured layer compared to a case where the resin component is only a non-curable resin. In addition, by using a curable compound in the primer layer, the durability of the cured layer (appearance after durability test, adhesion to the substrate, water slippage, etc.) tends to be excellent compared to a case where a non-curable compound is used. The curable compound includes active energy ray curable compounds and heat curable compounds, and active energy ray curable compounds are preferred. When the primer is applied to a resin substrate and then cured by heat, the resin substrate may be deformed by heat, but when the primer is cured by active energy rays, the deformation of the resin substrate by heat can be suppressed, so that the curable compound can be applied to resin substrates with low heat resistance. In addition, curing by active energy rays generally requires a shorter curing time than other curing methods such as heat curing and moisture curing, and can be expected to improve productivity.
[0184] As the active energy ray-curable compound, a conventionally known active energy ray-curable compound can be used, and examples thereof include compounds having a radical polymerizable group such as a (meth)acryloyl group. As the compound having a radical polymerizable group, various conventionally known compounds can be used, such as (meth)acrylate, other monomers copolymerizable with (meth)acrylate, etc. In addition, as the compound having a radical polymerizable group, a monofunctional compound having one radical polymerizable group, a bifunctional compound having two radical polymerizable groups, and a polyfunctional compound having three or more radical polymerizable groups, which is a trifunctional or higher functional compound, can be used. Among these, it is preferable to include a polyfunctional compound in order to make the primer layer have a high degree of curing in order to improve adhesion with the cured layer.
[0185] An example of the polyfunctional compound is a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate is not particularly limited, and examples thereof include (meth)acrylates having a skeleton derived from trimethylolpropane, such as pentaerythritol triacrylate, dipentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, and neopentyl glycol-modified trimethylolpropane di(meth)acrylate, (meth)acrylates having an isocyanurate skeleton, such as ditrimethylolpropane tetraacrylate and bis(2-acryloyloxyethyl)-2-hydroxyethyl isocyanurate; pentaerythritol triacrylate adduct to succinic anhydride, and dipentaerythritol adduct to succinic anhydride. Polyfunctional acrylates such as polytetramethylene glycol (PTMG) and hydroxyethyl acrylate (HEA) reactants, and polyfunctional urethane (meth)acrylates such as the reactant of hexamethylene diisocyanate (HDI) with PTMG and pentaerythritol triacrylate; polyester (meth)acrylates having carbonate bonds such as the reactant of oligoester using polycarbonate diol and pentaerythritol triacrylate; polyester (meth)acrylates having hydroxyl groups in the side chain or in the side chain and at the end (specifically, M8030, M7100, etc., manufactured by Toagosei); p) Polyurethane (meth)acrylates such as reaction products of acrylates; triethoxy (meth)acrylates having an isocyanurate ring such as triethoxyisocyanuric acid triacrylate; alkylene oxide modified products of these; and polycaprolactone modified products of these. Among these, from the viewpoints of viscosity, curability, and hardness of the cured film, preferred are pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol triacrylate; alkylene oxide modified products thereof; and caprolactone modified products thereof. The (meth)acrylates may be used alone or in combination of two or more.
[0186] Examples of the monofunctional compound include monofunctional (meth)acrylates, (meth)acrylic acid, etc. Examples of the monofunctional (meth)acrylates include, but are not limited to, alkyl (meth)acrylates such as methyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate, hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and methoxypropyl (meth)acrylate. alkoxyalkyl (meth)acrylates such as ethoxypropyl (meth)acrylate; aromatic (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate; amino group-containing (meth)acrylates such as diaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; ethylene oxide-modified (meth)acrylates such as methoxyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate and phenylphenol ethylene oxide-modified (meth)acrylate; glycidyl (meth)acrylate; and tetrahydrofurfuryl (meth)acrylate.
[0187] The difunctional polyfunctional (meth)acrylate is not particularly limited, but examples thereof include alkanediol di(meth)acrylates such as 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tricyclodecanedimethylol di(meth)acrylate, bisphenol-modified di(meth)acrylates such as bisphenol A ethylene oxide-modified di(meth)acrylate and bisphenol F ethylene oxide-modified di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, urethane di(meth)acrylate, epoxy di(meth)acrylate, alkylene oxide-modified products thereof, and polycaprolactone-modified products thereof.
[0188] As the thermosetting compound, a conventionally known thermosetting compound can be used, for example, a combination of various polyols and various polyisocyanates.
[0189] Examples of polyols include conventionally known ones, such as polymers such as polycarbonate polyol, polyester polyol, acrylic polyol, polyurethane polyol, polyolefin polyol, polyether polyol, and polyvinyl alcohol; polymers having a dendritic branched structure with a hydroxyl group at the end, such as dendrimers and hyperbranched polymers; and polymers such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, and 1,5-pentanediol. Examples of polyhydric alcohols include ethanol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, trimethylolethane, trimethylolpropane, glycerol, polycaprolactone triol, erythritol, pentaerythritol, polycaprolactone tetraol, and diglycerin.
[0190] Among these, polymer-type or branched polyols are preferred because they have a high crosslink density and excellent curability and durability. Among these, dendrimers and hyperbranched polymers are more preferred because they form a highly branched structure, effectively increasing the crosslink density and improving durability. These polyols may be used alone or in combination of two or more kinds.
[0191] Examples of the polyisocyanate include conventionally known ones, and examples thereof include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate; aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. Further, examples of the polyisocyanates include trifunctional or higher polyisocyanates such as biuret compounds, trimethylolpropane adduct compounds, isocyanurate compounds, allophanate compounds, etc., which are synthesized using these difunctional polyisocyanates as starting materials. These may be used alone or in combination of two or more kinds.
[0192] Among these, it is preferable to use a polyisocyanate having three or more functional groups, and more preferable to use an isocyanurate, because it increases the crosslink density and provides excellent curability and durability. From the viewpoint of durability of the cured layer, it is preferable to use an aromatic ring structure or an alicyclic structure, and from the viewpoint of resistance to yellowing, it is preferable to use an aliphatic structure or an alicyclic structure.
[0193] In the primer layer, the content of the resin component is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, relative to the total mass of the primer layer, and may be 100% by mass.
[0194] <Ultraviolet absorbing agent> Examples of the ultraviolet absorbing agent include organic ultraviolet absorbing agents and inorganic ultraviolet absorbing agents. From the viewpoint of transparency, the organic ultraviolet absorbing agents are preferred. The organic ultraviolet absorber is not particularly limited, but examples thereof include hydroxyphenyltriazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, cyclic iminoester ultraviolet absorbers, benzophenone ultraviolet absorbers, salicylic acid ester ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers. Among these, from the viewpoint of weather resistance and durability, hydroxyphenyltriazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, and cyclic iminoester ultraviolet absorbers are more preferred, and hydroxyphenyltriazine ultraviolet absorbers are even more preferred. These ultraviolet absorbers may be used alone or in combination of two or more. Furthermore, it is also possible to use those in which these compounds are incorporated into polymers.
[0195] Examples of hydroxyphenyltriazine-based ultraviolet absorbers include, but are not limited to, 2-[4-([2-hydroxy-3-dodecyloxypropyl]oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-([2-hydroxy-3-tridecyloxypropyl]oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (Tinuvin® 400). BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine with (2-ethylhexyl)-glycidic acid ester (Tinuvin® 405, BASF), 2,4-bis[2-hydroxy-4- butoxyphenyl"-6-(2,4-dibutoxyphenyl)-1,3-5-triazine (Tinuvin (registered trademark) 460, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol (Tinuvin (registered trademark) 1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (Tinuvin (registered trademark) 479, manufactured by BASF), and the like.
[0196] Benzotriazole-based ultraviolet absorbers include, but are not limited to, 2-[2'-hydroxy-5'-(methacryloyloxymethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxypropyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyhexyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-3'-tert-butyl-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-tert-butyl- 3'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-5-chloro-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-5-methoxy-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-5-cyano-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-5-tert-butyl-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-5-nitro-2H-benzotriazole, and the like.
[0197] Examples of the cyclic imino ester-based ultraviolet absorber include, but are not limited to, 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, 2-phenyl-3,1-benzoxazin-4-one, 2-(1- or 2-naphthyl)-3,1-benzoxazin-4-one, 2-(4-biphenyl)-3,1-benzoxazin-4-one, 2-p-nitrophenyl-3,1-benzoxazin-4-one, 2-m-nitrophenyl-3,1-benzoxazin-4-one, 2-p-benzoylphenyl-3,1-benzoxazin-4-one, 2-p-methoxyphenyl-3,1-benzoxazin-4-one, 2-o-methoxyphenyl-3,1-benzoxazin-4-one, 2-cyclohexyl-3, 1-benzoxazin-4-one, 2-p-(or m-)phthalimidophenyl-3,1-benzoxazin-4-one, N-phenyl-4-(3,1-benzoxazin-4-one-2-yl)phthalimide, N-benzoyl-4-(3,1-benzoxazin-4-one-2-yl)aniline, N-benzoyl-N-methyl-4-(3,1-benzoxazin-4-one-2-yl)aniline, 2-(p-(N-methylcarbonyl)phenyl)-3,1-benzoxazin-4-one, 2,2'-bis(3,1-benzoxazin-4-one), 2,2'-ethylenebis(3,1-benzoxazin-4-one), 2,2'-tetramethylenebis(3,1-benzoxazin-4-one), 2,2'-decamethylenebis(3,1-benzoxazin-4-one) , 2,2'-p-phenylenebis(3,1-benzoxazin-4-one), 2,2'-m-phenylenebis(3,1-benzoxazin-4-one), 2,2'-(4,4'-diphenylene)bis(3,1-benzoxazin-4-one), 2,2'-(2,6- or 1,5-naphthylene)bis(3,1-benzoxazin-4-one), 2,2'-(2-methyl-p-phenylene)bis(3,1-benzoxazin-4-one), 2,2'-(2-nitro-p-phenylene)bis(3,1-benzoxazin-4-one), 2,2'-(2-chloro-p-phenylene)bis(3,1-benzoxazin-4-one), 2,2'-(1,4-cyclohexylene)bis(3,1-benzoxazin-4-one), 1,3,5-tri(3,1-benzoxazin-4-one-2-yl)benzene, 1,3,5-tri(3,1-benzoxazin-4-one-2-yl)naphthalene, 2,4,6-tri(3,1-benzoxazin-4-one-2-yl)naphthalene, 2,8-dimethyl-4H,6H-benzo(1,2-d;5,4-d')bis(1,3)-oxazine-4,6-dione, 2,7-dimethyl-4H,9H-benzo(1,2-d;4,5-d')bis(1,3 )-oxazine-4,9-dione, 2,8-diphenyl-4H,8H-benzo(1,2-d;5,4-d')bis(1,3)-oxazine-4,6-dione, 2,7-diphenyl-4H,9H-benzo(1,2-d;4,5-d')bis(1,3)-oxazine-4,6-dione, 6,6'-bis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-bis(2-ethyl-4H,3,1-benzoxazine -4-one), 6,6'-bis(2-phenyl-4H,3,1-benzoxazin-4-one), 6,6'-methylenebis(2-methyl-4H,3,1-benzoxazin-4-one), 6,6'-methylenebis(2-phenyl-4H,3,1-benzoxazin-4-one), 6,6'-ethylenebis(2-methyl-4H,3,1-benzoxazin-4-one), 6,6'-ethylenebis(2-phenyl-4H,3,1-benzoxazin-4-one), benzoxazin-4-one), 6,6'-butylenebis(2-methyl-4H,3,1-benzoxazin-4-one), 6,6'-butylenebis(2-phenyl-4H,3,1-benzoxazin-4-one), 6,6'-oxybis(2-methyl-4H,3,1-benzoxazin-4-one), 6,6'-oxybis(2-phenyl-4H,3,1-benzoxazin-4-one), 6,6'-sulfonylbis(2-methyl 6,6'-sulfonylbis(2-phenyl-4H,3,1-benzoxazin-4-one), 6,6'-carbonylbis(2-methyl-4H,3,1-benzoxazin-4-one), 6,6'-carbonylbis(2-phenyl-4H,3,1-benzoxazin-4-one), 7,7'-methylenebis(2-methyl-4H,3,1-benzoxazin-4-one), 7,7'-Methylenebis(2-phenyl-4H,3,1-benzoxazin-4-one), 7,7'-bis(2-methyl-4H,3,1-benzoxazin-4-one), 7,7'-ethylenebis(2-methyl-4H,3,1-benzoxazin-4-one), 7,7'-oxybis(2-methyl-4H,3,1-benzoxazin-4-one), 7,7'-sulfonylbis(2-methyl-4H,3,1-benzoxazin-4-one), 7,7 '-Carbonylbis(2-methyl-4H,3,1-benzoxazin-4-one), 6,7'-bis(2-methyl-4H,3,1-benzoxazin-4-one), 6,7'-bis(2-phenyl-4H,3,1-benzoxazin-4-one, 6,7'-methylenebis(2-methyl-4H,3,1-benzoxazin-4-one), 6,7'-methylenebis(2-phenyl-4H,3,1-benzoxazin-4-one), etc.
[0198] Benzophenone-based ultraviolet absorbers (benzophenone-based compounds) and oxybenzophenone-based ultraviolet absorbers (oxybenzophenone-based compounds) include, for example, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydrous and trihydrate), 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone (trade name "KEMISORB111", manufactured by Chemipro Chemical Co., Ltd.), 2,2',4,4'-tetrahydroxybenzophenone (trade name "SEESORB106", manufactured by Shipro Chemical Co., Ltd.), and 2,2'-dihydroxy-4,4-dimethoxybenzophenone.
[0199] Examples of salicylic acid ester-based ultraviolet absorbers (salicylic acid ester-based compounds) include phenyl-2-acryloyloxybenzoate, phenyl-2-acryloyloxy-3-methylbenzoate, phenyl-2-acryloyloxy-4-methylbenzoate, phenyl-2-acryloyloxy-5-methylbenzoate, phenyl-2-acryloyloxy-3-methoxybenzoate, phenyl-2-hydroxybenzoate, phenyl-2-hydroxy-3-methylbenzoate, phenyl-2-hydroxy-4-methylbenzoate, phenyl-2-hydroxy-5-methylbenzoate, phenyl-2-hydroxy-3-methoxybenzoate, 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate (Tinuvin (registered trademark) 120, manufactured by BASF), and the like.
[0200] Examples of cyanoacrylate-based ultraviolet absorbers (cyanoacrylate-based compounds) include alkyl-2-cyanoacrylates, cycloalkyl-2-cyanoacrylates, alkoxyalkyl-2-cyanoacrylates, alkenyl-2-cyanoacrylates, and alkynyl-2-cyanoacrylates.
[0201] <Light stabilizer> The light stabilizer is not particularly limited, but examples thereof include amine-based light stabilizers, phenol-based light stabilizers, phosphorus-based light stabilizers, and thioether-based light stabilizers. Among these, amine-based light stabilizers, phenol-based light stabilizers, and phosphorus-based light stabilizers are preferred, and amine-based light stabilizers are more preferred in consideration of less yellowing. These light stabilizers can be used alone or in combination of two or more. It is also possible to use a polymer incorporating these compounds.
[0202] Examples of the amine-based light stabilizer include a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol (Tinuvin (registered trademark) 622, manufactured by BASF), a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol and N,N',N'',N'''-tetrakis-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diazin-2-yl)-4,7-diazadecane-1,10-diazin-2-yl, and the like. 1:1 reaction product of dibutylamine with 1,3-triazine (Tinuvin® 119, BASF), polycondensate of dibutylamine·1,3-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine (Tinuvin® 2020, BASF), poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2-4-diyl}{2,2,6,6-tetramethyl-4-piperidyl}isopropylamine] imino]hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}) (Tinuvin® 944, manufactured by BASF), mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate (Tinuvin® 765, manufactured by BASF), bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate (Tinuvin® 770, manufactured by BASF), bis(2,2,6,6-tetramethyl-4-piperidyl)decanedioate -1-(octyloxy)-4-piperidinyl) ester, reaction products of 1,1-dimethylethyl hydroperoxide with octane (Tinuvin® 123, BASF), bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate (Tinuvin® 144, BASF), cyclohexane and N-butyl 2,2,6,6-tetramethyl-4-piperidinamine-2,4,6-trichloro-1,3,Examples of such amine-based light stabilizers include a reaction product of 5-triazine with 2-aminoethanol (Tinuvin® 152, manufactured by BASF), a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate (Tinuvin® 292, manufactured by BASF), and a mixed ester of 1,2,3,4-butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane (ADK STAB LA63P, manufactured by ADEKA). Among these amine-based light stabilizers, hindered amine-based stabilizers are particularly preferred due to their excellent performance.
[0203] Examples of phenol-based light stabilizers include 2,6-di-tertiary butyl-4-methylphenol, 4-hydroxymethyl-2,6-di-tertiary butylphenol, 2,6-di-tertiary butyl-4-ethylphenol, butylated hydroxyanisole, n-octadecyl-3-(4-hydroxy-3,5-di-tertiary butylphenyl)propionate, distearyl-(4-hydroxy-3-methyl-5-tertiary butyl)benzyl malonate, tocopherol, 2,2'-methylenebis(4-methyl-6-tertiary butylphenol), 2,2'-methylenebis(4-ethyl-6-tertiary butylphenol), 4,4'-methylenebis(2,6-di-tertiary butylphenol), 4,4'-butylidenebis(6-tertiary butyl-m-cresol), 4,4'-thiobis(6-tertiary butyl-m-cresol), ), styrenated phenol, N,N'-hexamethylenebis(3,5-di-tertiary butyl-4-hydroxyhydrocinnamide, bis(3,5-di-tertiary butyl-4-hydroxybenzylphosphonic acid ethyl ester)calcium, 1,1,3-tris(2-methyl-4-hydroxy-5-tertiary butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tertiary butyl-4-hydroxybenzyl)benzene, tetrakis[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionyloxymethyl]methane, 1,6-hexanediol-bis[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionate], 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, triethylene glycol-bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], 2,2'-oxamide bis[ethyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-dioctylthio-1,3,5-trimethyl-2 ... riazine, bis[2-tertiary butyl-4-methyl-6-(2-hydroxy-3-tertiary butyl-5-methylbenzyl)phenyl]terephthalate, 3,9-bis{2-[3-(3-tertiary butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, 3,9-bis{2-[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, and the like.
[0204] Examples of phosphorus-based light stabilizers include trisnonylphenyl phosphite, tris(2,4-di-tertiary butylphenyl) phosphite, tris[2-tertiary butyl-4-(3-tertiary butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl] phosphite, tridecyl phosphite, octyl diphenyl phosphite, di(decyl) monophenyl phosphite, di(tridecyl) pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, di(nonylphenyl) pentaerythritol diphosphite, bis(2,4-di-tertiary butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tertiary butyl-4-methylphenyl) pentaerythritol diphosphite, bis(2,4 ,6-tri-tertiary butylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4'-n-butylidenebis(2-tertiary butyl-5-methylphenol)diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tertiary butylphenyl)butane triphosphite, tetrakis(2,4-di-tertiary butylphenyl)biphenylene diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2-[(2,4,8,10-tetrakis-tertiary butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]ethyl)amine, and the like.
[0205] Examples of the thioether-based light stabilizer include dialkyl thiodipropionate compounds such as dilauryl, dimyristyl, and distearyl thiodipropionate; and β-alkyl mercaptopropionate compounds of polyols such as tetrakis[methylene(3-dodecylthio)propionate]methane.
[0206] <Other additives> Examples of other additives include leveling agents, silane coupling agents, defoamers, thickeners, antistatic agents, infrared absorbing agents, foaming agents, inorganic fine particles, organic fine particles, dyes, pigments, antioxidants, anti-yellowing agents, bluing agents, anti-fogging agents, anti-settling agents, and adhesion imparting agents.
[0207] The Martens hardness of the primer layer at 23°C is 50 to 300 N / mm 2 is preferable, 100 to 250N / mm2 is more preferable, and 150 to 200N / mm 2 When the Martens hardness is equal to or greater than the above lower limit, the adhesion to the upper layer tends to be improved, and when it is equal to or less than the above upper limit, the adhesion to the lower layer tends to be improved. The method for measuring the Martens hardness is as described in the Examples section below. The Martens hardness of the primer layer can be adjusted by the type of resin component constituting the primer layer, the crosslink density, and the like.
[0208] The contact angle of 1 μL of distilled water at 23° C. on the surface of the primer layer (hereinafter also referred to as the “water contact angle”) is preferably 100° or less, more preferably 95° or less, and even more preferably 90° or less. If the water contact angle is equal to or less than the above upper limit, the wettability when forming a cured layer on the primer layer is improved, and the adhesion between the primer layer and the cured layer is also improved. There is no particular restriction on the lower limit of the water contact angle, but it is preferably 1° or more. The method for measuring the contact angle with water is as described in the Examples section below. The water contact angle can be adjusted by the amount of leveling agent added, the content of raw materials having hydrophilic groups (hydroxyl groups, amino groups, sulfonyl groups, carboxyl groups, and salts thereof, etc.), etc. Specifically, the water contact angle tends to decrease when the amount of leveling agent added is reduced, when a leveling agent with a low surface tension reducing ability is used, or when the content of raw materials having hydrophilic groups is increased.
[0209] The thickness of the primer layer is preferably 0.01 to 30 μm, more preferably 0.5 to 20 μm, and further preferably 1 to 20 μm. When the thickness of the primer layer is equal to or more than the lower limit, the adhesion between the substrate and the cured layer is superior, and when the thickness is equal to or less than the upper limit, the appearance tends to be superior.
[0210] <Method of manufacturing laminate> The present laminate can be produced, for example, by forming a primer layer on a substrate (primer layer forming step), coating the primer layer with a curable composition containing the copolymer (A) and at least one silane compound (b) or a component (B) consisting of a partial hydrolysis condensate thereof, and curing the composition to form a cured layer (cured layer forming step).
[0211] <Primer layer formation process> The primer layer may be formed, for example, by applying a primer containing a resin component and a diluent onto the substrate and then drying to remove the diluent. The primer preferably contains at least one selected from the group consisting of an ultraviolet absorber and a light stabilizer. The primer may contain additives other than the ultraviolet absorber and the light stabilizer, if necessary, within the range that does not impair the effects of the present invention. The resin component, ultraviolet absorber, light stabilizer, and other additives are as described above.
[0212] The diluent may be water, an organic solvent, or the like. Examples of organic solvents include alcohol-based solvents, glycol-based solvents, hydrocarbon-based solvents, ester-based solvents, ketone-based solvents, and ether-based solvents. Examples of alcohol-based solvents include methanol, ethanol, isopropyl alcohol, n-butanol, isobutanol, octanol, n-propyl alcohol, and acetylacetone alcohol. Examples of glycol-based solvents include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-propyl ether, ethylene glycol mono n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monomethyl ether acetate. Examples of hydrocarbon-based solvents include benzene, kerosene, toluene, and xylene. Examples of ester-based solvents include methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, and ethyl acetoacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, acetylacetone, etc. Examples of the ether solvent include ethyl ether, butyl ether, methyl cellosolve, ethyl cellosolve, dioxane, furan, tetrahydrofuran, etc. The organic solvent may be used alone or in combination of two or more kinds.
[0213] In the primer, the content of the resin component is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, relative to 100% by mass of the non-volatile components of the primer, and may be 100% by mass.
[0214] The content of the UV absorber varies depending on the type of UV absorber, but is preferably 30 mass% or less, more preferably 0.01 to 20 mass%, even more preferably 0.1 to 15 mass%, and particularly preferably in the range of 0.3 to 15 mass%, relative to 100 mass% of the non-volatile components of the primer.
[0215] The content of the light stabilizer varies depending on the type of light stabilizer, but is preferably 30% by mass or less, more preferably 0.01 to 20% by mass, even more preferably 0.1 to 15% by mass, and particularly preferably 0.3 to 15% by mass, relative to 100% by mass of the non-volatile components of the primer.
[0216] The concentration of the non-volatile components in the entire primer is not particularly limited, but is preferably 80% by mass or less, more preferably 0.1 to 70% by mass, even more preferably 10 to 70%, and particularly preferably 20 to 60%. By using the non-volatile components in the above range, a curable composition with excellent coatability can be obtained.
[0217] The primer can be prepared by mixing a resin component, a diluent, and, if necessary, an ultraviolet absorber, a light stabilizer, and other additives.
[0218] Examples of the coating method that can be used include known methods such as brush coating, gravure coating, die coating, bar coating, spray coating, flow coating, dip coating, spin coating, and curtain coating. The curing method may be the same as that described above, and a method in which the curable composition is irradiated with active energy rays is preferred.
[0219] When the curable composition contains a diluent, after the curable composition is applied to a substrate, the curable composition may be subjected to a heat treatment for drying in order to remove the diluent before being irradiated with active energy rays. The heat treatment for drying can be performed by irradiation with a near-infrared lamp, circulation of hot air, or the like.
[0220] The cured layer obtained by irradiating active energy rays after heat treatment tends to have improved adhesion over a long period outdoors compared to that obtained without heat treatment, since the diluent is unlikely to remain inside the cured layer. From the viewpoint of the appearance and adhesion of the cured layer, the drying conditions are preferably a temperature of 40 to 90°C, more preferably 50 to 70°C, and the drying time is preferably 60 to 180 seconds, more preferably 90 to 150 seconds.
[0221] The curable composition may be subjected to a heat treatment after being irradiated with active energy rays. This heat treatment can be performed by irradiation with a near-infrared lamp, circulation of hot air, etc. The cured layer obtained by performing a heat treatment after curing by irradiation with active energy rays has a higher condensation reaction rate than that obtained without the heat treatment, and therefore tends to have excellent hardness and durability.
[0222] The sliding angle of 20 μL of water at 23° C. on the surface of the hardened layer (initial hardened layer) formed as described above is preferably lower, and is preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the sliding angle of water, and it is 0° or more. If the sliding angle of water is equal to or less than the above upper limit, raindrops or snow adhering to the surface slide off easily.
[0223] Furthermore, the water sliding angle after the durability test is particularly important in the development of a wide range of applications, and the lower the angle the better, and the less change there is from the initial state the better. After forming the cured layer as described above and carrying out a durability test for 96 hours under conditions of 50°C and 99% RH or more, the sliding angle of 20 μL of water at 23°C on the surface of the cured layer (cured layer after durability test) is preferably 60° or less, more preferably 50° or less, even more preferably 40° or less, particularly preferably 30° or less, and most preferably 20° or less. There is no particular restriction on the lower limit of the sliding angle of water, and it is, for example, 1° or more. The change amount of the water sliding angle of the cured product layer after the durability test from the water sliding angle of the initial cured product layer (the water sliding angle of the cured product layer after the durability test - the water sliding angle of the initial cured product layer) is preferably 40° or less, more preferably 30° or less, still more preferably 20° or less, and most preferably 15° or less. There is no particular lower limit, but it is preferably 0°. By setting it within this range, the performance comparable to the initial stage can be exhibited over a long period of time, and the product design becomes easy.
[0224] In the laminate described above, since the cured product layer is composed of a cured product of a resin composition containing the copolymer (A) and the component (B), it is excellent in appearance, water repellency and durability.
[0225] This laminate can be used for sensing member applications such as members through which electromagnetic waves of sensing members (millimeter wave radar, LiDAR, etc.) pass; various lamp lenses (vehicle lamps) of automobiles, resin glazing, road signs, traffic signals, camera lenses, 5G-related members, antennas, solar panels, window glass, resin glass, automotive glass, etc. Among the above applications of this laminate, the sensing member application is particularly suitable.
Examples
[0226] Examples and comparative examples are shown below to explain the present invention in more detail, but the present invention is not limited thereto. "Parts" in the description represents "parts by mass". Measurement and evaluation were performed by the following methods.
[0227] [Measurement and Evaluation Methods] <Measurement of Mw> In this example, the Mw of the copolymer and the partial hydrolyzate condensate of the silane compound produced was measured by gel permeation chromatography (GPC) under the following conditions. Equipment: "e2695" manufactured by Waters, Column: "TSKgel Super H3000+H4000+H6000" manufactured by Tosoh, Detector: Differential refractive index detector (RI detector / built-in), Solvent: Tetrahydrofuran, Temperature: 40℃, Flow rate: 0.5mL / min, Injection volume: 10μL, Concentration: 0.2% by mass, Calibration sample: monodisperse polystyrene, Calibration method: polystyrene equivalent.
[0228] <Appearance> The appearance of the evaluation sample was evaluated visually, and the judging criteria were as follows: (Judgment criteria) A: No abnormalities such as whitening, cracks, or blisters are observed, and a transparent, smooth coating film has been formed. B: Slight abnormalities such as whitening, cracks, and swelling are observed. C: Abnormalities such as whitening, cracks, and swelling are observed.
[0229] <Coating strength> The cured film surface of the evaluation sample was strongly rubbed back and forth three times with the thumb nail of the evaluator's dominant hand in an atmosphere of 23° C. and 55% RH. The degree of scratching of the cured film was visually evaluated according to the following criteria. A: No change in appearance. B: It will get scratched. C: The coating peels off.
[0230] <Sliding property> The cured film surface of the evaluation sample was evaluated for its water sliding property by measuring the sliding angle of 20μL of water at 23℃ by intermittently tilting the substrate using the sliding method. Specifically, in an environment of 23℃ and 50%RH, a droplet of 20μL of distilled water was dropped onto the cured film surface of the evaluation sample placed horizontally on a sample fixing table using a contact angle meter (DM-500, Kyowa Interface Science Co., Ltd.), and then the evaluation sample was intermittently tilted at 1° increments, and the inclination angle at which the droplet began to slide was taken as the sliding angle. The criteria for water sliding property are as follows: (Judgment criteria) A: The sliding angle is greater than 1° and less than 40°. B: The sliding angle is greater than 41° and less than 60°. C: Water droplets do not slide down even when the inclination angle exceeds 60° or is 90°.
[0231] <Martens hardness> The Martens hardness of the primer layer at 23°C was measured under the following test conditions using a FISCHERSCOPE (registered trademark) HM2000 manufactured by Fisher Instruments. (Test conditions) Indenter: Vickers indenter Load increase parameter: dSQRT(F) / dt = constant Maximum load: 1mN Load application time = 20 seconds Creep = 0 seconds Load reduction parameter: dSQRT(F) / dt = constant
[0232] The primer layer to be used for measuring the Martens hardness was prepared under the following conditions. (How to prepare test specimens) Base material: polycarbonate plate (PC, 3 mm thick), Coating: spray coating, Dry film thickness: 13μm, Curing conditions: If the primer is active energy ray curable, use a high pressure mercury lamp at 2000mJ / cm 2 If the primer is heat-curing, 120°C for 30 minutes. The Martens hardness value varies depending on the type of substrate and the film thickness.
[0233] <Contact angle> The contact angle of water was measured by the sessile drop method. Specifically, 1 μL of distilled water was dropped onto the surface of the cured layer (or the surface of the primer layer before the cured layer was formed) of the evaluation sample placed horizontally in an environment of 23° C. and 50% RH using a contact angle meter (DM-500, manufactured by Kyowa Interface Science Co., Ltd.), and the contact angle (static contact angle) was measured 5 seconds after the drop.
[0234] <Adhesion> The adhesion of the cured layer (adhesion between the primer layer and the cured layer) was evaluated by peeling with cellophane tape. Specifically, cellophane tape was pressed with a finger onto the surface of the cured layer of the evaluation sample in an environment of 23°C and 50% RH, and quickly peeled off in a direction at an angle of 45° toward the user. The area of the peeled cured layer (peeled area) was visually confirmed to evaluate the adhesion. The evaluation criteria for adhesion are as follows. A: No peeling. B: Peeling is observed, but the peeled area is less than 50% of the adhered area of the cellophane tape. C: The peeled area is 50% or more of the adhered area of the cellophane tape.
[0235] <Durability> The cured films of the evaluation samples were subjected to a durability test for 96 hours using a humidity tester (device name: humidity tester, model CT-3H, manufactured by Suga Test Instruments Co., Ltd.) under conditions of a chamber temperature of 50°C and a chamber humidity of 99% RH or higher. After the durability test, the above-mentioned appearance and water slipping property were evaluated.
[0236] <Weather resistance> The weather resistance test was performed using a weather resistance tester (device name: Super Xenon Weather Meter, model SX75, manufactured by Suga Test Instruments Co., Ltd.) with 12 minutes of rainfall out of 60 minutes and irradiation intensity of 180 W / m 2 A weather resistance test was carried out for 500 hours under the conditions of (300-400 nm), black panel temperature 63°C, chamber temperature 50°C, and chamber humidity 50%. The evaluation sample was placed so that the laminated cured film surface was perpendicular to the light source side of the weather resistance tester.
[0237] [Abbreviation] The abbreviations used below have the following meanings: KBM-5103: "KBM-5103" manufactured by Shin-Etsu Chemical Co., Ltd. (3-acryloxypropyltrimethoxysilane, 100% non-volatile components). FM-0721: "Silaplane FM-0721" manufactured by JNC Corporation (polydimethylsiloxane having a methacryloyl group at one end, Mw 4200, 100% non-volatile components). FM-0711: "Silaplane FM-0711" manufactured by JNC Corporation (polydimethylsiloxane having a methacryloyl group at one end, Mw 900, 100% non-volatile components). The structures of FM-0721 and FM-0711 are as follows: CH2=C(CH3)-COO-C3H6-(Si(CH3)2O) n -(CH2)3CH3
[0238] Copolymer (A-1): the copolymer obtained in Synthesis Example 1 described below (FM-0721:KBM5103=30:70 (mass ratio), Mw 16,200). Copolymer (A-2): the copolymer obtained in Synthesis Example 2 described below (FM-0721:KBM5103=50:50 (mass ratio), Mw 19,800). Copolymer (A-3): the copolymer obtained in Synthesis Example 3 described below (FM-0711:KBM5103=30:70 (mass ratio), Mw 15,500). Copolymer (A-4): the copolymer obtained in Synthesis Example 4 described below (FM-0711:KBM5103=30:40 (mass ratio), Mw 43,000). Copolymer (E-1): The copolymer obtained in Synthesis Example 5 described below (FM-0721:KBM-5 103=0:100 (mass ratio), Mw23400). Copolymer (E-2): The copolymer obtained in Synthesis Example 6 described below (FM-0721:KBM-5 103=20:30 (mass ratio), Mw53300).
[0239] Component (B-1): Alkoxysilane hydrolysis condensate (Mw 1000) obtained in Synthesis Example 7 described below. Component (B-2): Alkoxysilane hydrolysis condensate (Mw 1600) obtained in Synthesis Example 8 described below. MS51: "MS51" manufactured by Mitsubishi Chemical Corporation (tetramethoxysilane partial hydrolysis condensate, Mw 800-1100, 100% non-volatile components).
[0240] Photoacid generator: San-Apro "CPI-200K" (p-phenylthiophenyldiphenylsulfonium hexafluorophosphate, 50% non-volatile components). IPA: 2-propanol. PGM: propylene glycol monomethyl ether. Perocta O: "Perocta O" (1,1,3,3-tetramethylbutyl 2-ethylhexaneperoxy acid) manufactured by NOF Corporation.
[0241] [Method of preparing polymer] The methods for preparing the copolymers and partial hydrolysis condensates of silane compounds used in the examples and comparative examples are described below. Note that copolymers (A-1) to (A-4) are copolymers (A), while copolymers (E-1) and (E-2) are comparative products that do not correspond to copolymer (A).
[0242] <Synthesis Example 1: Preparation of Copolymer (A-1)> 73.0g of KBM-5103, 41.7g of FM-0721, 264.9g of PGM, and 0.52g of Perocta O were added to a 1000mL five-neck separable flask equipped with a stirrer, a dropping funnel, a cooling condenser, and a thermometer. In addition, 73.0g of KBM-5103, 20.9g of FM-0721, 225.3g of PGM, and 0.52g of Perocta O were added to the dropping funnel. Next, the flask was set in an oil bath, stirring was started under a nitrogen atmosphere, and the temperature was raised until the internal temperature reached 85°C. 30 minutes after the internal temperature reached 85°C, the monomer mixture was dropped from the dropping funnel over 2 hours and held for 1 hour, after which 0.21g of Perocta O was added, and 1 hour later, 0.21g of Perocta O was further added, and the reaction was carried out for 5 hours, followed by cooling. The resulting product was a polymer having a weight average molecular weight (Mw) of 16,200 and a non-volatile content of 30%.
[0243] <Synthesis Example 2: Preparation of Copolymer (A-2)> 50.0g of KBM-5103, 60.0g of FM-0721, 254.0g of PGM, and 0.50g of Perocta O were added to a 1000mL five-neck separable flask equipped with a stirrer, a dropping funnel, a cooling condenser, and a thermometer. 50.0g of KBM-5103, 40.0g of FM-0721, 216.0g of PGM, and 0.50g of Perocta O were added to the dropping funnel. Next, the flask was set in an oil bath, stirring was started under a nitrogen atmosphere, and the temperature was raised until the internal temperature reached 85°C. 30 minutes after the internal temperature reached 85°C, the monomer mixture was dropped from the dropping funnel over 2 hours and held for 1 hour, after which 0.20g of Perocta O was added, and 1 hour later, 0.20g of Perocta O was further added, and the reaction was allowed to proceed for 5 hours, after which it was cooled. The resulting product was a polymer having a weight average molecular weight (Mw) of 19,800 and a non-volatile content of 30%.
[0244] <Synthesis Example 3: Preparation of Copolymer (A-3)> 73.0g of KBM-5103, 41.7g of FM-0711, 264.9g of PGM, and 0.52g of Perocta O were added to a 1000mL five-neck separable flask equipped with a stirrer, a dropping funnel, a cooling condenser, and a thermometer. In addition, 73.0g of KBM-5103, 20.9g of FM-0711, 225.3g of PGM, and 0.52g of Perocta O were added to the dropping funnel. Next, the flask was set in an oil bath, stirring was started under a nitrogen atmosphere, and the temperature was raised until the internal temperature reached 85°C. 30 minutes after the internal temperature reached 85°C, the monomer mixture was dropped from the dropping funnel over 2 hours and held for 1 hour, after which 0.21g of Perocta O was added, and 1 hour later, 0.21g of Perocta O was further added, and the reaction was allowed to proceed for 5 hours, after which it was cooled. The resulting product was a polymer having a weight average molecular weight (Mw) of 15,500 and a non-volatile content of 30%.
[0245] <Synthesis Example 4: Preparation of Copolymer (A-4)> 41.7g of KBM-5103, 41.7g of FM-0721, 20.9g of n-butyl methacrylate, 10.4g of 2-hydroxyethyl methacrylate, 267.7g of PGM, and 0.52g of Perocta O were placed in a 1000mL five-neck separable flask equipped with a stirrer, a dropping funnel, a cooling condenser, and a thermometer. Also, 41.7g of KBM-5103, 20.9g of FM-0721, 20.9g of n-butyl methacrylate, 10.4g of 2-hydroxyethyl methacrylate, 222.2g of PGM, and 0.52g of Perocta O were placed in the dropping funnel. Next, the flask was set in an oil bath, stirring was started under a nitrogen atmosphere, and the internal temperature was raised to 85°C. Thirty minutes after the internal temperature reached 85°C, the monomer mixture was added dropwise from the dropping funnel over a period of two hours, and after maintaining the temperature for one hour, 0.21 g of Perocta O was added, and one hour later, another 0.21 g of Perocta O was added, and the reaction was continued for five hours before cooling. The product obtained was a polymer with a non-volatile content of 30% and a weight average molecular weight (Mw) of 43,000.
[0246] <Synthesis Example 5: Preparation of Copolymer (E-1)> 110.0g of KBM-5103, 254.0g of PGM, and 0.50g of Perocta O were added to a 1000mL five-neck separable flask equipped with a stirrer, a dropping funnel, a cooling condenser, and a thermometer. 90.0g of KBM-5103, 216.0g of PGM, and 0.50g of Perocta O were added to the dropping funnel. Next, the flask was set in an oil bath, stirring was started under a nitrogen atmosphere, and the temperature was raised until the internal temperature reached 85°C. 30 minutes after the internal temperature reached 85°C, the monomer mixture was dropped from the dropping funnel over 2 hours and held for 1 hour, after which 0.20g of Perocta O was added, and 1 hour later, 0.20g of Perocta O was further added, and the reaction was allowed to proceed for 5 hours, after which it was cooled. The resulting product was a polymer having a non-volatile content of 30% and a weight average molecular weight (Mw) of 23,400.
[0247] <Synthesis Example 6: Preparation of Copolymer (E-2)> 31.3g of KBM-5103, 12.5g of FM-0721, 41.7g of n-butyl methacrylate, 10.4g of 2-hydroxyethyl methacrylate, 225.1g of PGM, and 0.52g of Perocta O were added to a 1000mL five-neck separable flask equipped with a stirrer, a dropping funnel, a cooling condenser, and a thermometer. Also, 31.3g of KBM-5103, 29.2g of FM-0721, 41.7g of n-butyl methacrylate, 10.4g of 2-hydroxyethyl methacrylate, 264.8g of PGM, and 0.52g of Perocta O were added to the dropping funnel. Next, the flask was set in an oil bath, stirring was started under a nitrogen atmosphere, and the internal temperature was raised to 85°C. Thirty minutes after the internal temperature reached 85°C, the monomer mixture was added dropwise from the dropping funnel over a period of two hours, and after maintaining the temperature for one hour, 0.21 g of Perocta O was added, and one hour later, another 0.21 g of Perocta O was added, and the reaction was continued for five hours before cooling. The product obtained was a polymer with a non-volatile content of 30% and a weight average molecular weight (Mw) of 53,300.
[0248] <Synthesis Example 7: Preparation of component (B-1)> 308 g of MS51 was mixed with 624 g of methanol, 65 g of water, and 3 g of aluminum acetylacetonate (III), and stirred at room temperature for 3 days to obtain a colorless, transparent, uniform liquid solution of component (B-1) (SiO2 equivalent concentration of component (B-1): 16 wt%).
[0249] <Synthesis Example 8: Preparation of component (B-2)> 308 g of MS51 was mixed with 624 g of methanol, 65 g of water, and 3 g of aluminum acetylacetonate (III), and stirred at room temperature for 7 days to obtain a colorless, transparent, uniform liquid solution of component (B-2) (SiO2 equivalent concentration of component (B-2): 16 wt%).
[0250] [Example 1] <Preparation of Resin Composition> A resin composition was prepared by mixing 3.5 parts of copolymer (A-1), 4.2 parts of component (B-1), 10 parts of IPA, 10 parts of PGM, and 0.04 parts of photoacid generator CPI-200K (manufactured by San-Apro Co., Ltd.).
[0251] <Preparation of evaluation samples> The obtained resin composition was spray-coated on the surface of a 3 mm-thick polycarbonate resin plate (PC plate) (manufactured by Mitsubishi Engineering Plastics Corporation, product name: "IUPILON ML-300") so that the thickness after drying would be 0.7 μm, and then the coating was dried (the solvent was volatilized) by heating for 120 seconds in a hot air dryer preheated to 60° C. Next, the dried coating was irradiated with 1000 mJ / cm2 in an air atmosphere using a high-pressure mercury lamp (manufactured by Eye Graphics, USX5-0902). 2 The coating was cured by exposure to ultraviolet light (the cumulative exposure dose at wavelengths of 340 to 380 nm was measured using an ultraviolet actinometer UV-351 (manufactured by Oak Seisakusho)), to obtain an evaluation sample in which a cured film of the resin composition was laminated on the PC board.
[0252] <Evaluation> The curability of the obtained resin composition was evaluated. In addition, the initial appearance and water slippage of the obtained evaluation sample (before the durability test) and the appearance and water slippage of the obtained evaluation sample after the durability test were evaluated. The results are shown in Table 1.
[0253] [Examples 2 to 7, Comparative Examples 1 to 5, Reference Example 1] Compositions were prepared and evaluation samples were produced in the same manner as in Example 1, except that the types and amounts (parts) of components blended in the compositions were as shown in Tables 1 and 2. The evaluation results of the compositions and evaluation samples are shown in Tables 1 and 2. However, in Comparative Example 5, the compatibility of the composition in a liquid state was low, and it was not possible to mold it into a cured film, so that no evaluation sample was produced or evaluated.
[0254] [Examples 8 to 10] A composition was prepared in the same manner as in Example 1, except that the types and amounts (parts) of the components blended in the composition were as shown in Table 1. Using this composition, an evaluation sample was prepared in the same manner as in Example 1, except that the substrate was changed from a PC plate to a glass plate having a thickness of 5 mm. The evaluation results of the composition and the evaluation sample are shown in Table 1.
[0255] [Reference example 2] A composition was prepared and an evaluation sample was prepared in the same manner as in Reference Example 1, except that in preparing the evaluation sample, the composition was spray-coated and then cured by heating for 10 seconds in a hot air dryer preheated to 150° C. without irradiating with ultraviolet light. The evaluation results of the composition and the evaluation sample are shown in Table 2.
[0256] [Example 11] <Preparation of Curable Composition> A curable composition was prepared by mixing 3.5 parts of the solution of copolymer (A-1), 4.2 parts of the solution of component (B-1), 10 parts of IPA, 10 parts of PGM, and 0.04 parts of the photoacid generator CPI-200K.
[0257] <Primer preparation> 0.9 parts of benzophenone as a photopolymerization initiator, 3 parts of Tinuvin 400 (manufactured by BASF) as an ultraviolet absorber, and 0.15 parts of Tinuvin 123 (manufactured by BASF) as a light stabilizer were added to a resin mixture of 22 parts of a caprolactone modified dipentaerythritol hexaacrylate (DPHA) ("DPCA-20" manufactured by Nippon Kayaku Co., Ltd.) and 16 parts of urethane acrylate. The mixture was then diluted with propylene glycol monomethyl ether to a non-volatile content of 32% by mass to prepare an active energy ray-curable primer (1). The urethane acrylate was prepared as follows. In a flask equipped with a dropping funnel with a heat retention function, a reflux condenser, a stirring blade and a temperature sensor, 530g (2mol) of dicyclohexylmethane diisocyanate and 300ppm of di-n-butyltin dilaurate were charged and heated to 40°C. Then, 650g (1mol) of 800g (weight average molecular weight 800) of polycarbonate diol (trade name: Kuraray Polyol C-770, manufactured by Kuraray Co., Ltd.) was dropped over 4 hours as a polyol compound. After stirring at 40°C for 2 hours, the temperature was raised to 70°C over 1 hour. Then, 232g (2mol) of 2-hydroxyethyl acrylate (HEA) was dropped over 2 hours, and the mixture was stirred for another 2 hours to obtain urethane acrylate. The obtained product was a polymer with a non-volatile content of 75% and a molecular weight of 1500.
[0258] <Preparation of evaluation sample (laminate)> The primer (1) was spray-coated on a 3 mm-thick polycarbonate resin plate (PC plate) (manufactured by Mitsubishi Engineering Plastics Corporation, product name: "IUPILON ML-300"), and then the coating was dried (the solvent was volatilized) by heating for 90 seconds in a hot air dryer preheated to 70°C. Next, the dried coating was irradiated with 2000 mJ / cm2 using a high-pressure mercury lamp in an air atmosphere. 2 The coating was cured by irradiating it with ultraviolet light (the cumulative irradiation amount at wavelengths of 340 to 380 nm was measured using an ultraviolet actinometer UV-351 (manufactured by Oak Seisakusho)) to form a primer layer with a thickness of 13 μm. Next, the curable composition was spray-coated on the primer layer so that the thickness after drying was 700 nm, and then the coating was dried (the solvent was volatilized) by heating for 120 seconds in a hot air dryer preheated to 60° C. Next, the dried coating was irradiated with 1000 mJ / cm 2 using a high-pressure mercury lamp (USX5-0902, manufactured by Eye Graphics) in an air atmosphere. 2 The coating was cured by irradiating it with ultraviolet light (the cumulative irradiation amount at wavelengths of 340 to 380 nm was measured using an ultraviolet actinometer UV-351 (manufactured by Oak Seisakusho)). This produced a laminate in which a primer layer and a cured layer were laminated in this order on the PC board.
[0259] <Evaluation> The obtained evaluation samples were evaluated for initial appearance (before durability test), adhesion, contact angle, and sliding angle, and for appearance, adhesion, contact angle, and sliding angle after durability test. The results are shown in Table 3.
[0260] [Examples 12, 13, 16, Comparative Examples 6 to 9] Compositions and evaluation samples were prepared in the same manner as in Example 11, except that the types and amounts (parts) of components blended in the compositions were as shown in Tables 3 and 4. The evaluation results of the compositions and evaluation samples are shown in Tables 3 and 4.
[0261] [Example 14] 100 parts of Basonol (registered trademark) HPE1170B (manufactured by BASF) as a polyol, 30 parts of Kuraray Polyol C-1090 (manufactured by Kuraray), 159 parts of Duranate MHG-80B (manufactured by Asahi Kasei Corporation) as an isocyanate, 70 parts of MEK-ST-40 (manufactured by Nissan Chemical Industries, Ltd.) as inorganic fine particles, 30 parts of Tinuvin 405 (manufactured by BASF) as an ultraviolet absorber, 0.5 parts of Tinuvin 152 (manufactured by BASF) as a light stabilizer, and 0.05 parts of dibutyltin dilaurate (DBTDL) as a curing accelerator catalyst were mixed uniformly, and further diluted with cyclohexanone and MIBK so that the non-volatile component concentration was about 32%, to prepare a thermosetting primer (2). An evaluation sample was prepared in the same manner as in Example 11, except that when forming the primer layer, primer (2) was spray-coated so that the thickness of the coating film after curing was 10 μm, and a cured film (primer layer) was formed by heat treatment at 120° C. for 30 minutes. The evaluation results are shown in Table 3.
[0262] [Example 15] 16 parts of BR-83 (manufactured by Mitsubishi Chemical Corporation) as a non-curing acrylic resin, 2.2 parts of Tinuvin PS (manufactured by BASF Corporation) as an ultraviolet absorber, and 1.8 parts of Tinuvin 123 (manufactured by BASF Corporation) as a light stabilizer were diluted with PGM and methyl ethyl ketone (MEK) to a non-volatile component concentration of 16%, and mixed uniformly to prepare primer (3). An evaluation sample was prepared in the same manner as in Example 11, except that when forming the primer layer, primer (3) was spray-coated so that the thickness of the coating film after drying was 10 μm, and a non-curable coating film (primer layer) was formed by heat treatment at 90° C. for 30 minutes. The evaluation results are shown in Table 3.
[0263] [Example 17] An evaluation sample was prepared in the same manner as in Example 11, except that a 100 μm thick polycarbonate film (PC film, FE-2000 manufactured by Mitsubishi Engineering Plastics) was used instead of the PC plate, and when forming the primer layer and the cured layer, the primer (1) and the resin composition described in Example 12 were applied onto the PC film using a bar coater so that the thickness after drying would be 10 μm and 700 nm, respectively. The evaluation results are shown in Table 3.
[0264] [Example 18] A 50 μm thick polyethylene terephthalate film (PET film, Diafoil T600E50 W07 manufactured by Mitsubishi Chemical) was used instead of the PC plate, and when forming the primer layer and the cured layer, the primer (1) and the resin composition described in Example 12 were applied onto the PET film using a bar coater so that the thickness after drying was 10 μm and 700 nm, respectively. An evaluation sample was prepared in the same manner as in Example 11. The evaluation results are shown in Table 3.
[0265] [Example 19] <Preparation of Curable Composition> A curable composition was prepared by mixing 3.5 parts of copolymer (A-1), 4.2 parts of component (B-1), 10 parts of IPA, and 10 parts of PGM.
[0266] <Preparation of evaluation samples> The curable composition was spray-coated onto a 5 mm-thick glass plate so that the thickness after curing would be 0.7 μm, and the composition was heated in a hot air dryer at 150° C. for 1 hour to cure, thereby obtaining an evaluation sample in which a cured film was laminated on the glass plate.
[0267] <Evaluation> The obtained evaluation samples were evaluated for initial appearance and water sliding property (before the weather resistance test) and for appearance and water sliding property after the weather resistance test. The results are shown in Table 5.
[0268] [Examples 20 and 21, Comparative Examples 10 to 13] Curable compositions were prepared and evaluation samples were produced in the same manner as in Example 19, except that the types and amounts (parts) of components blended in the curable compositions were as shown in Table 5. The evaluation results of the evaluation samples are shown in Table 5. However, in Comparative Example 13, a cured film could not be formed, so no evaluation was performed.
[0269] [Example 22] Curable compositions were prepared in the same manner as in Example 1, except that the types and amounts (parts) of the components blended in the curable compositions were as shown in Table 5. The obtained curable composition was spray-coated on a 5 mm thick glass plate so that the thickness after curing would be 0.7 μm, and then the coating was dried (the solvent was volatilized) by heating for 120 seconds in a hot air dryer preheated to 60° C. Next, the dried coating was irradiated with 1000 mJ / cm 2 in an air atmosphere using a high-pressure mercury lamp (USX5-0902, manufactured by Eye Graphics). 2 The coating film was cured by irradiating it with ultraviolet light (the cumulative irradiation amount at wavelengths of 340 to 380 nm was measured using an ultraviolet actinometer UV-351 (manufactured by Oak Seisakusho)), to obtain a laminate in which a cured film was laminated on a glass plate. The evaluation results of the evaluation sample are shown in Table 5.
[0270] [Table 1]
[0271] [Table 2]
[0272] [Table 3]
[0273] [Table 4]
[0274] [Table 5]
[0275] In Tables 1 to 5, the content of each component is the amount including the volatile matter. In the evaluation of "water sliding", "x" means that the droplets did not move on the cured film surface even when the inclination angle was changed to 90°, and the sliding angle could not be measured. "-" means that the cured film surface was hydrophilic, so no droplets were formed and the sliding angle could not be measured. "N / A" means that the measurement was not possible due to the influence of the surface condition of the coating film, etc.
[0276] As shown in Table 1, the cured products of the compositions of Examples 1 to 10 had excellent appearance and water slip properties both initially and after the durability test. On the other hand, the composition of Comparative Example 1 did not contain a copolymer that imparts water sliding properties, and the surface of the cured film was hydrophilic, so as shown in Table 2, it was impossible to determine the water sliding properties. The composition of Comparative Example 2 did not contain component (B), and therefore the appearance of the cured film was poor, as shown in Table 2. In addition, the hardness of the cured film was low. The composition of Comparative Example 3 used a copolymer that did not contain a polydimethylsiloxane unit, which is a component that imparts water-sliding property, and therefore, as shown in Table 2, had low water-sliding property. The composition of Comparative Example 4 used a copolymer with a low content of polydimethylsiloxane units, which are components that impart water-sliding properties, and therefore, as shown in Table 2, had low water-sliding properties. In the composition of Comparative Example 5, the components of the copolymer (A-1) were added as monomers without being copolymerized, and therefore the compatibility in the liquid state was low, and as shown in Table 2, it was not possible to form a cured film.
[0277] As shown in Table 3, the laminates of Examples 11 to 18 were excellent in adhesion between the substrate and the cured layer, and in the appearance, water slippage, hardness and hardness of the cured layer. Furthermore, in Examples 11 to 14 and 16 to 18, the appearance and water slippage of the cured layer after the durability test were also good, and the durability was excellent. On the other hand, the laminate of Comparative Example 6, which did not contain component (B), had a poor appearance as shown in Table 4. In addition, the curability was poor, the coating strength was poor, and the laminate did not function as a cured film. The laminate of Comparative Example 7 did not contain the copolymer (A), and therefore, as shown in Table 4, was poor in water sliding property. The laminate of Comparative Example 8 used a copolymer that did not contain a polydimethylsiloxane unit, which is a component that imparts water-sliding property, and therefore, as shown in Table 4, had low water-sliding property. The laminate of Comparative Example 9 used a copolymer with a low content of polydimethylsiloxane units, which are components that impart water-sliding properties, and therefore, as shown in Table 4, had poor water-sliding properties and poor appearance.
[0278] As shown in Table 5, the cured films of Examples 19 to 22 were excellent in appearance and water slippage both initially and after the weather resistance test. On the other hand, the cured film of Comparative Example 10 did not contain a copolymer that imparts water sliding property, and the surface of the cured film was hydrophilic, so as shown in Table 5, it was impossible to judge the water sliding property. The cured film of Comparative Example 11 did not contain component (B), and therefore had a poor appearance as shown in Table 5. In addition, the curability was poor, the coating strength was poor, and the film did not function as a cured film. The cured film of Comparative Example 12 used a copolymer not containing a polyalkylsiloxane unit, which is a component that imparts water slippage, and therefore, as shown in Table 5, had low water slippage. In Comparative Example 13, the components of copolymer (A-1) were not copolymerized but were added to the curable composition as monomers. As a result, as shown in Table 5, the compatibility in the liquid state was low and the composition could not be molded into a cured film.
Claims
1. The present invention comprises a copolymer (A) including a structural unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a structural unit based on a monomer (Y) having a group represented by the following formula (1), and a component (B) consisting of a silane compound or a partial hydrolysis condensate thereof, the sum of the proportion of structural units based on said silicone macromonomer (X) and the proportion of structural units based on said monomer (Y) is 55 mass% or more relative to the total mass of all structural units constituting said copolymer (A); the proportion of the structural units based on the monomer (Y) is 40 to 85% by mass relative to the total mass of all structural units constituting the copolymer (A); a resin composition in which the proportion of structural units based on said silicone macromonomer (X) is 15 to 60 mass % relative to the total mass of all structural units constituting said copolymer (A). -R 1 -M(R 2 ) r (OR 3 ) m-r ・・・(1) In the above, M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta; R 1 represents a hydrocarbon group having 1 to 5 carbon atoms; R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and when m-r is 2 or more, (m-r) OR 3 may be different from each other.
2. The resin composition according to claim 1, wherein the component (B) comprises at least one silane compound represented by the following formula (b) or a partial hydrolysis condensate thereof: R 4 4-n Si(OR 5 ) n ・・・(b) However, R 4 represents a hydrogen atom, an alkyl group, an aryl group, or an aralkyl group; R 5 represents an alkyl group or a phenyl group, n represents an integer of 2 to 4, and n OR 5 may be different from each other, and when n is 2, (4-n) R 4 may be different from each other.
3. The resin composition according to claim 1 or 2, wherein the silicone macromonomer (X) has a weight average molecular weight of 500 to 40,000.
4. The resin composition according to any one of claims 1 to 3, wherein the weight average molecular weight of the copolymer (A) is 3,000 to 400,000.
5. The resin composition according to any one of claims 1 to 4, wherein the weight average molecular weight of the component (B) is 500 or more.
6. The resin composition according to any one of claims 1 to 5, wherein the component (B) is a partial hydrolysis condensate of a tetraalkoxysilane.
7. The resin composition according to any one of claims 1 to 6, wherein the component (B) is a secondary reaction product obtained by subjecting at least one partial hydrolysis condensation product of the silane compound, the partial hydrolysis condensation product having a weight average molecular weight of 300 to 3000, to a hydrolysis condensation reaction in the presence of a catalyst.
8. The resin composition according to any one of claims 1 to 7, further comprising an initiator (C).
9. The resin composition according to claim 8 , wherein the initiator (C) is a photopolymerization initiator.
10. The resin composition according to claim 8 or 9, wherein the initiator (C) comprises at least one selected from the group consisting of a photoacid generator and a photobase generator.
11. The resin composition according to any one of claims 1 to 10, which is used for a sensing component application.
12. A cured product of the resin composition according to any one of claims 1 to 11.
13. A laminate having a substrate and a layer made of a cured product, The cured product is a cured product of a composition comprising: a copolymer (A) including a structural unit based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and a structural unit based on a monomer (Y) having a group represented by the following formula (1); and a component (B) consisting of a silane compound or a partial hydrolysis condensate thereof: the proportion of the structural units based on the monomer (Y) is 40 to 85% by mass relative to the total mass of all structural units constituting the copolymer (A); the proportion of structural units based on the silicone macromonomer (X) is 15 to 60 mass% relative to the total mass of all structural units constituting the copolymer (A); A laminate in which a durability test is carried out for 96 hours under conditions of a tank temperature of 50°C and a tank humidity of 99% RH or more, and then the sliding angle of 20 μL of distilled water at 23°C on the surface of a layer made of the cured product is measured by tilting the laminate with an intermittent tilt that changes the tilt angle intermittently by 1°, and the sliding angle is 60° or less on the surface of the layer made of the cured product. -R 1 -M(R 2 ) r (OR 3 ) m-r ・・・(1) In the above, M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta; R 1 represents a hydrocarbon group having 1 to 5 carbon atoms; R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and when m-r is 2 or more, (m-r) OR 3 may be different from each other.
14. The laminate according to claim 13 , further comprising a primer layer provided on the substrate, and a layer made of the cured product provided on the primer layer.
15. The present invention relates to a copolymer (A) that includes a structural unit based on a silicone macromonomer (X) that includes a polyalkylsiloxane unit and a structural unit based on a monomer (Y) that includes a group represented by the following formula (1), a component (B) that includes a silane compound or a partial hydrolysis condensate thereof, and a photopolymerization initiator, the proportion of the structural units based on the monomer (Y) is 40 to 85% by mass relative to the total mass of all structural units constituting the copolymer (A); a resin composition in which the proportion of structural units based on said silicone macromonomer (X) is 15 to 60 mass % relative to the total mass of all structural units constituting said copolymer (A). -R 1 -M(R 2 ) r (OR 3 ) m-r ・・・(1) In the above, M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta; R 1 represents a hydrocarbon group having 1 to 5 carbon atoms; R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and when m-r is 2 or more, (m-r) OR 3 may be different from each other.
16. The present invention relates to a copolymer (A) that includes a structural unit based on a silicone macromonomer (X) that includes a polyalkylsiloxane unit and a structural unit based on a monomer (Y) that includes a group represented by the following formula (1), a component (B) that includes a silane compound or a partial hydrolysis condensate thereof, and a photopolymerization initiator, the proportion of the structural units based on the monomer (Y) is 40 to 85% by mass relative to the total mass of all structural units constituting the copolymer (A); A cured product of a resin composition, wherein the proportion of structural units based on the silicone macromonomer (X) is 15 to 60 mass % relative to the total mass of all structural units constituting the copolymer (A). -R 1 -M(R 2 ) r (OR 3 ) m-r ・・・(1) In the above, M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta; R 1 represents a hydrocarbon group having 1 to 5 carbon atoms; R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; and when r is 2 or more, r R 2 may be different from each other, and when m-r is 2 or more, (m-r) OR 3 may be different from each other.
17. The present invention relates to a method for producing a cured product, the method comprising the steps of: curing, by heat treatment or active energy ray irradiation, a resin composition comprising: a copolymer (A) which contains constituent units based on a silicone macromonomer (X) containing a polyalkylsiloxane unit and constituent units based on a monomer (Y) having a group represented by the following formula (1), the proportion of the constituent units based on the monomer (Y) being 40 to 85 mass% and the proportion of the constituent units based on the silicone macromonomer (X) being 15 to 60 mass% relative to the total mass of all constituent units; and a component (B) which contains a silane compound or a partial hydrolysis condensate thereof: -R 1 -M(R 2 ) r (OR 3 ) m-r ・・・(1) In the above, M represents Al, Fe, In, Ge, Hf, Si, Ti, Sn, Zr, or Ta; R 1 represents a hydrocarbon group having 1 to 5 carbon atoms; R 2 represents an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aryl group; R 3 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, an aryl group, or an acyl group; m represents an integer of 3 to 4 according to M; r represents an integer of 0 to 3; when r is 2 or more, r R2s may be different from each other; when m-r is 2 or more, (m-r) OR 3 may be different from each other.
Citation Information
Patent Citations
Highly weatherproof coating
JP1986151272A
Magnetic recording medium
JP1987052715A
Coating agent for mold release
JP1987059672A
Impregnatable waterproofing composition
JP1995179849A
Curable composition and its preparation
JP1996143773A